Can cost-effectiveness analysis integrate concerns for equity? Systematic review - Johri, Mira; Norheim, Ole Frithjof (International Journal of Technology Assessment in Health Care, 2012)
OBJECTIVES: The aim of this study was to promote approaches to health technology assessment (HTA) that are both evidence-based and values-based. We conducted a systematic review of published studies describing formal methods to consider equity in the context of cost-effectiveness analysis (CEA). METHODS: Candidate studies were identified through an unrestricted search of the Pub Med and EMBASE databases. The search closed on January 20, 2011. We identified additional studies by consulting experts and checking article bibliographies. Two authors independently reviewed each candidate study to determine inclusion and extracted data from studies retained for review. In addition to documenting methods, data extraction identified implicit and explicit notions of fairness. Data were synthesized in narrative form. Study quality was not assessed. RESULTS: Of the 695 candidate articles, 51 were retained for review. We identified three broad methods to facilitate quantitative consideration of equity concerns in economic evaluation: integration of distributional concerns through equity weights and social welfare functions, exploration of the opportunity costs of alternative policy options through mathematical programming, and multi-criteria decision analysis. CONCLUSIONS: Several viable techniques to integrate equity concerns within CEA now exist, ranging from descriptive approaches to the quantitative methods studied in this review. Two obstacles at the normative level have impeded their use in decision making to date: the multiplicity of concepts and values discussed under the rubric of equity, and the lack of a widely accepted normative source on which to ground controversial value choices. Clarification of equity concepts and attention to procedural fairness may strengthen use of these techniques in HTA decision making.
KerkoCite.ItemAlsoKnownAs: 10.1017/s0266462312000050 10/f3xtd7 2339240:IWXV98J3 2405685:PSE2A7W4
Keywords: Canada; Cost-Benefit Analysis; Decision Support Techniques; Health Resources; Health Services Accessibility; Health Status Disparities; Humans; Quality-Adjusted Life Years; Social Justice; Social Welfare

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10837295 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1018 ZenodoArchiveConcept: 10837294
Keywords: _r:AddedByMyEducationEvidence

Cost-effectiveness with equity: Raising learning for marginalised girls through Camfed's programme in Tanzania - Sabates, Ricardo; Rose, Pauline; Delprato, Marcos; Alcott, Benjamin (Policy Paper No. 18/2 (REAL Centre, University of Cambridge, 2018), 2018)
This policy paper provides a cost-effectiveness analysis of Camfed’s programme in Tanzania. Camfed’s programme adopts a multidimensional approach that is aimed at reaching marginalised girls at risk of dropping out from secondary schools by using interventions that are aimed at both increasing their chances of staying in school and learning.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1247315 2339240:844SXSWR 2339240:NJNE53N8 2405685:PGA6QWXT 2405685:VQQK7F6G
Keywords: ___working_potential_duplicate; _not_EdTechHub

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Publisher: Routledge _eprint: https://doi.org/10.1080/19439342.2020.1844782 KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1844782 2339240:IZUVIXVI 2405685:NV3ND4MJ
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Publisher: Routledge _eprint: https://doi.org/10.1080/19439342.2020.1844782 KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1844782 2339240:FRZIQURK 2405685:VBG6JSIG
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Cost Effectiveness of Interactive Radio Instruction Program Karnataka: Basic and Program Cost Effectiveness - Bakshi, Shubhashansha (eSocialSciences, 2011)
The Program CEA extends to the study to an impact analysis of the Radio programs to assess whether the expenditure being made for this intervention is helping the students in improving their learning outcomes. This would then serve as a true measure of effectiveness that is; linking the outreach with the outcomes. This requires tracking a cohort of treatment and control groups over a period of three years. Also the study has documented the qualitative behaviour as observed in these groups. URL:[http://cbps.in/Publications.aspx].
Publication Title: Working Papers KerkoCite.ItemAlsoKnownAs: 2339240:L8345RND 2405685:ESR8WZQI
Keywords: Attendance; CEA; Central Tendency; Cost Effectiveness; Enrolment; Interactive Radio Instruction Program; Karnataka; Qualitative analysis; Research; Teachers; cohort of treatment; data; outcomes; qualitative behaviour; school; villages

Affordability and cost-effectiveness: decision-making on the cost-effectiveness plane - Sendi, P. P.; Briggs, A. H. (Health Economics, 2001)
Much recent research interest has focused on handling uncertainty in cost-effectiveness analysis and in particular the calculation of confidence intervals for incremental cost-effectiveness ratios (ICERs). Problems of interpretation when ICERs are negative have led to two important and related developments: the use of the net-benefit statistic and the presentation of uncertainty in cost-effectiveness analysis using acceptability curves. However, neither of these developments directly addresses the problem that decision-makers are constrained by a fixed-budget and may not be able to fund new, more expensive interventions, even if they have been shown to represent good value for money. In response to this limitation, the authors introduce the affordability curve which reflects the probability that a programme is affordable for a wide range of threshold budgets. The authors argue that the joint probability an intervention is affordable and cost-effective is more useful for decision-making since it captures both dimensions of the decision problem faced by those responsible for health service budgets.
Number: 7 Publisher: John Wiley and Sons KerkoCite.ItemAlsoKnownAs: 10.1002/hec.639 2339240:SXUMKWQZ 2405685:CQBIWZXP

Session 6: How do I ensure my EdTech investments are cost-effective? - Chuang, Rachel; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341519 ZenodoArchiveConcept: 7341518 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341460 10.5281/zenodo.7341519 10.53832/edtechhub.0140 2405685:CUFS8JJE 2405685:CWKPJR8R
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14260074 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1078 ZenodoArchiveConcept: 14260073
Keywords: _r:AddedByMyEducationEvidence

Resolving the “Cost-Effective but Unaffordable” Paradox: Estimating the Health Opportunity Costs of Nonmarginal Budget Impacts - Lomas, James; Claxton, Karl; Martin, Stephen; Soares, Marta (Value in Health, 2018)
Considering whether or not a proposed investment (an intervention, technology, or program of care) is affordable is really asking whether the benefits it offers are greater than its opportunity cost. To say that an investment is cost-effective but not affordable must mean that the (implicit or explicit) “threshold” used to judge cost-effectiveness does not reflect the scale and value of the opportunity costs. Existing empirical estimates of health opportunity costs are based on cross-sectional variation in expenditure and mortality outcomes by program budget categories (PBCs) and do not reflect the likely effect of nonmarginal budget impacts on health opportunity costs. The UK Department of Health regularly updates the needs-based target allocation of resources to local areas of the National Health Service (NHS), creating two subgroups of local areas (those under target allocation and those over). These data provide the opportunity to explore how the effects of changes in health care expenditure differ with available resources. We use 2008–2009 data to evaluate two econometric approaches to estimation and explore a range of criteria for accepting subgroup specific effects for differences in expenditure and outcome elasticities across the 23 PBCs. Our results indicate that health opportunity costs arising from an investment imposing net increases in expenditure are underestimated unless account is taken of likely nonmarginal effects. They also indicate the benefits (reduced health opportunity costs or increased value-based price of a technology) of being able to “smooth” these nonmarginal budget impacts by health care systems borrowing against future budgets or from manufacturers offering “mortgage” type arrangements.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jval.2017.10.006 2339240:LGRL2L6H 2405685:XZML4VWY

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

Cost-effective approaches to improve global learning: What does recent evidence tell us are “Smart Buys” for improving learning in Low and Middle Income Countries? - World Bank; Foreign, Commonwealth & Development Office; BE2 (2020)
Cost-Effective Approaches to Improve Global Learning : What Does Recent Evidence Tell Us Are “Smart Buys” for Improving Learning in Low and Middle Income Countries? (English)
KerkoCite.ItemAlsoKnownAs: 2339240:7TWW5LH3 2339240:DREGRHNB 2339240:LB976C9V 2339240:PXVB6XAN 2339240:X6IKG4D9 2339240:ZN5GIACQ 2405685:78HTA35E 2405685:7WSML8I6 2405685:EM4K4F3G 2405685:J5BTUHXI 2405685:PXQZNUIT 2405685:QBC6GINK 2405685:YQRZUMFC 2405685:ZE34D622 2534378:DWVFIYUY 4042040:VSZTKCHW

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:5U948655 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (International Journal of Educational Development, 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
EdTechHub.Copy: 2129771:QHYYISLI shortDOI: 10/f8t8wn KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2016.03.006 10/f8t8wn 2129771:QHYYISLI 2339240:45CT95ZX 2339240:59F29QUS 2339240:AKA34H48 2339240:ERJRDYGR 2339240:JWWGS2FM 2339240:VHERHC8U 2339240:W2IRHE4N 2405685:6GPCWMKY 2405685:DH6QGZK3 2405685:DSJ268AF 2405685:HNU98RFR 2405685:NAH85KGQ 2405685:RJ64GDLT 2405685:T6BQBZK6 2405685:Y3YWXGDF 2534378:DA5UA4C3 2534378:IQ2QU9ZM 2534378:NFIYL9F6
Keywords: Education policy; International education; Kenya; Literacy; Reading; Technology; __:import:01; __:match:final; __:matched; __:study_id:2457283; ___working_potential_duplicate; __finaldtb

Cost-Effectiveness Measurement in Development: Accounting for Local Costs and Noisy Impacts - Evans, David K.; Popova, Anna (The World Bank, 2014)
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-7027 2339240:9TRQJA7R 2405685:MNGE8QKW

When cost-effective interventions are unaffordable: Integrating cost-effectiveness and budget impact in priority setting for global health programs - Bilinski, Alyssa; Neumann, Peter; Cohen, Joshua; Thorat, Teja; McDaniel, Katherine; Salomon, Joshua A. (PLOS Medicine, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1371/journal.pmed.1002397 2339240:DPDBP8UV 2405685:G3W2NWX3

Planning for the Total Cost of Edtech Initiatives - edWeb (edWeb, 2019)
Strategic planning for edtech is an endless journey—and not just because of constantly evolving hardware and software. Upgrading infrastructure, device maintenance, and ongoing professional development, in addition to program and device costs, mean tech initiatives need permanent budget lines that take into account the total cost. In the edWebinar, “Strategic Technology Planning and Investment,” which is part of CoSN’s Empowered Superintendent series for edWeb, three superintendents who’ve been in the trenches for all aspects of district edtech plans discussed effective financial planning for technology.
KerkoCite.ItemAlsoKnownAs: 2339240:M3CJMVFE 2405685:D6RP9ZAL

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Piper, Benjamin; Jepkemei, Evelyn; Kwayumba, Dunston; Kibukho, Kennedy (FIRE: Forum for International Research in Education, 2015)
Kenya is investing in information and communication technology (ICT) to improve children's learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students. All three showed significant impacts in English and Kiswahili above the results of the control group. The impacts of the three interventions were not statistically significantly different from each other. Based on the findings, we recommend that Kenyan policy makers embed ICT interventions in a larger instructional reform, using ICT to support particular instructional improvement challenges. We also suggest that policy makers incorporate empirically derived cost-effectiveness analysis into investment decisions, to ensure that ICT provides value for money.
shortDOI: 10/ggjkvv KerkoCite.ItemAlsoKnownAs: 10.18275/fire201502011025 10/ggjkvv 2339240:APPT498R 2339240:D5IHJW9H 2339240:E5GA8GCG 2339240:EK3GAM3J 2339240:G6TBKSGI 2339240:IYCXFMIU 2405685:5IT5XZNT 2405685:DAU3FLGU 2405685:H9RNSJQE 2405685:J45J4EMF 2405685:V6F62IW5 2405685:WVNEPIB3 2405685:Y4AUMNW2 2534378:73A9DFAH 2534378:8Y5PJAGB 2534378:P2EJKSKD
Keywords: African Languages; Control Groups; Cost Effectiveness; ERIC; Current Index to Journals in Education (CIJE); Educational Policy; Educational Practices; Elementary Secondary Education; English (Second Language); Experimental Groups; Foreign Countries; Handheld Devices; Intervention; Kenya; Literacy; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Student Improvement; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096974; ___working_potential_duplicate; __finaldtb

Low-cost educational messaging in West Africa: evidence on cost-effectiveness - Mitchell, Joel; Mukankusi, Aimée; D'Rozario, Jonny (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12519241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1033 ZenodoArchiveConcept: 12519240
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Comparative Cost-Effectiveness Analysis to Inform Policy in Developing Countries: A General Framework with Applications for Education - Dhaliwal, Iqbal; Duflo, Esther; Glennerster, Rachel; Tulloch, Caitlin (Education policy in developing countries, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:DG9Q8TQF 2405685:YEG3692Q

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00071005.2012.756170 KerkoCite.ItemAlsoKnownAs: 10.1080/00071005.2012.756170 2339240:4YZ6K9I8 2405685:X94EP2P8
Keywords: ___working_potential_duplicate; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00071005.2012.756170 KerkoCite.ItemAlsoKnownAs: 10.1080/00071005.2012.756170 2339240:4YZ6K9I8 2405685:X94EP2P8
Keywords: ___working_potential_duplicate; auto_merged; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

Smart buys, great sales and special offers: cost-effective approaches to improve global learning - Lewin, Keith; Learning | 0; Learning | 0 (The Education and Development Forum (UKFIET), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4GZPTGRL 2405685:7CGSPQI6

The True Cost of Freemiums in Edtech - Levine, Elliott (EdTech Digest, 2019)
An industry veteran has some on-point advice about what you pay for and what you get. GUEST COLUMN | by Elliott Levine They say, “the best things in life are free,” but that is not always the case. With education technology (edtech), sometimes the cost of “free” ends up being unreasonably high in the long […]
KerkoCite.ItemAlsoKnownAs: 2339240:I9AWBSIU 2405685:SXL6X7IC

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:IL3G2LER 2339240:IQT7LI8P 2405685:9YMXHH74 2405685:CN86U6UQ 2405685:LX2STYUZ

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

What are the impacts and cost-effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries? Systematic review - Orr, David; Westbrook, Jo; Pryor, John; Durrani, Naureen; Sebba, Judy; Adu-Yeboah, Christine (EPPI-Centre, Social Science Research Unit, Institute of Education, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:K82B5UP3 2339240:NN7K3HRQ 2405685:5J3HIZH9 2405685:YAT9NL4R
Keywords: C:Low- and middle-income countries

The Effect of Computer-Assisted Learning on Students’ Long-Term Development - Bianchi, Nicola; Lu, Yi; Song, Hong (Social Science Research Network, 2020)
In this paper, we examine the effect of computer-assisted learning on students’ long-term development. We explore the implementation of the “largest ed-tech intervention in the world to date,” which connected China’s best teachers to more than 100 million rural students through satellite internet. We find evidence that exposure to the program improved students’ academic achievement, labor performance, and computer usage. We observe these effects up to ten years after program implementation. These findings indicate that education technology can have long-lasting positive effects on a variety of outcomes and can be effective in reducing the rural–urban education gap.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3309169 2339240:ZHPK63EW 2405685:9H5R8VY2
Keywords: China; computer-assisted education; education policy; education quality; education technology

The relationship between educational television and mathematics capability in Tanzania - Watson, Joe; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2021)
Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low-income countries when delivered in controlled settings. However, existing research in low-resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of normal television exposure. This paper, therefore, investigates the relationship between normal exposure to a popular Tanzania-produced cartoon, Ubongo Kids and mathematics capability, as represented by plausible values derived from an item response theory model applied to children’s test responses. Cross-sectional investigation of a sample of 38 682 Tanzanian children suggested normal educational television exposure to be significantly associated with mathematics capability, when controlling for age, sex, school enrolment, Kiswahili attainment and household fixed effects. While cross-sectional results are not necessarily causal, the findings in this paper broadly correspond with those from previous designs using repeated observations. What is more, considering association results alongside cost and viewership estimates suggests television-based interventions to be highly cost effective. Practitioner Notes What is already known about this topic National data for Tanzania suggests the country to have both low levels of mathematics proficiency and considerable access to television technology. Educational television-based interventions might, therefore, be worthy of consideration by educational policymakers, especially given that studies conducted in controlled settings indicate that television can deliver learning benefits. There is, however, little evidence concerning educational television exposure outside of controlled settings. Only one such study in a low-income context that concerned the association between learning outcomes and viewing among primary-age children has been identified. What this paper adds This paper addresses this dearth of research by investigating the association between normal exposure to a Tanzanian cartoon, Ubongo Kids and mathematics capability, as derived from an item response theory model applied to the test responses of 38 682 children. Cross-sectional findings suggest the association between normal television exposure and mathematics capability to be significant. Further, a cost-effectiveness comparison with alternate interventions in comparable contexts indicates that educational television is highly cost-effective. Implications for practice and/or policy The findings presented in this paper concerning educational television viewership in usual environments act to triangulate those from prior research conducted in controlled settings. As such, policymakers in low-income contexts now possess more convincing evidence on the potential influence of educational television interventions. Additionally, the cost-effectiveness comparison made suggests that educational television should be considered a viable option by policymakers seeking to address learning outcomes with limited resources.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13047 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 2339240:7RAS7H3N 2405685:MVRBU5UB
Keywords: Tanzania; cost effectiveness; educational television; mathematics

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 10.17863/cam.54714 2339240:6LGJJU8F 2339240:MVL3KA6H 2339240:U3SHRB68 2339240:XZDCXAZ7 2405685:8WKWEBZZ 2405685:A5XKUF3W 2405685:CHDUKI36 2405685:VJ8U5IDE 2405685:YENK6ASB
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found

How to Improve Education Outcomes Most Efficiently? A Comparison of 150 Interventions Using the New Learning-Adjusted Years of Schooling Metric - Angrist, Noam; Evans, David K.; Filmer, Deon; Glennerster, Rachel; Rogers, F. Halsey; Sabarwal, Shwetlena (The World Bank, 2020)
Many low- and middle-income countries lag far behind high-income countries in educational access and student learning. Limited resources mean that policymakers must make tough choices about which investments to make to improve education. Although hundreds of education interventions have been rigorously evaluated, making comparisons between the results is challenging. Some studies report changes in years of schooling; others report changes in learning. Standard deviations, the metric typically used to report learning gains, measure gains relative to a local distribution of test scores. This metric makes it hard to judge if the gain is worth the cost in absolute terms. This paper proposes using learning-adjusted years of schooling (LAYS)—which combines access and quality and compares gains to an absolute, cross-country standard—as a new metric for reporting gains from education interventions. The paper applies LAYS to compare the effectiveness (and cost-effectiveness, where cost is available) of interventions from 150 impact evaluations across 46 countries. The results show that some of the most cost-effective programs deliver the equivalent of three additional years of high-quality schooling (that is, schooling at quality comparable to the highest-performing education systems) for just $100 per child—compared with zero years for other classes of interventions.
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-9450 2129771:TUR7B4UV 2339240:3LCE9HV8 2339240:438DD95Z 2339240:98FSI5XH 2339240:PRN4F3XJ 2339240:S527VEKP 2339240:SNZZPXZE 2339240:TSZ5USU5 2405685:2W6J6E78 2405685:52GAJX48 2405685:59W7LV77 2405685:67PNDWSU 2405685:E7BQQ8AY 2405685:PJMJJZIG 2405685:W96R4GKX 2405685:X53U5NLR 2405685:XF4XK3C6 2534378:RYREI3A2 2534379:2C73YQ47
Keywords: Cost-Benefit Analysis; Education Outcomes; Government Policy; Impact Evaluation; Learning Loss; Learning-Adjusted Years of Schooling; Public Expenditure; Years of Schooling; ___working_potential_duplicate; ⛔ No DOI found

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.
KerkoCite.ItemAlsoKnownAs: 2339240:MMWPL7JY 2405685:NEXA5KQM

Reimagining Girls' Education: Solutions to keep girls learning in emergencies - Guglielmi, Silvia; Jones, Nicola; Nicolai, Susan; Pereznieto, Paola; Plank, Georgia; Vu, Nhung; Sanchez-Tapia, Ingrid; Mackintosh, Alasdair (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:34NUHRTZ 2339240:8ZNTUL5A 2405685:MZB8Q7PA 2405685:TSIVULXP
Keywords: Access to Education; Barriers; Context Effect; Cost Effectiveness; Costs; Disadvantaged Youth; Distance Education; Educational Finance; Educational Technology; Emergency Programs; Equal Education; Evidence Based Practice; Females; Foreign Countries; Gender Bias; Inclusion; Intervention; Planning; Sex Fairness; Sex Stereotypes; Teaching Methods; Technology Uses in Education

Mobile-based system for cost-effective e-learning contents delivery in resource and bandwidth constrained learning environments - Mahenge, Michael P. J.; Mwangoka, Joseph W. (Knowledge Management & E-Learning: An International Journal, 2014)
The advancement in Information and Communication Technologies (ICTs) has brought opportunities for the development of Smart Cities. The Smart City uses ICT to enhance performance and wellbeing, to reduce costs and resource consumption, and to engage more effectively and actively with its citizens. In particular, the education sector is adopting new ways of learning in Higher Education Institutions (HEIs) through e-learning systems. While these opportunities exist, e-learning content delivery and accessibility in third world countries like Tanzania is still a challenge due to resource and network constrained environments. The challenges include: high cost of bandwidth connection and usage; high dependency on the Internet; limited mobility and portability features; inaccessibility during the offline period and shortage of ICT facilities. In this paper, we investigate the use of mobile technology to sustainably support education and skills development particularly in developing countries. Specifically, we propose a Cost-effective Mobile Based Learning Content Delivery system for resource and network constrained environments. This system can be applied to cost-effectively broaden and support education in many cities around the world, which are approaching the 'Smart City' concept in their own way, even with less available technology infrastructure. Therefore, the proposed solution has the potential to reduce the cost of the bandwidth usage, and cut down the server workload and the Internet usage overhead by synchronizing learning contents from some remote server to a local database in the user’s device for offline use. It will also improve the quality of experience and participation of learners as well as facilitate mobility and portability in learning activities, which also supports the all-compassing learning experience in a Smart City.https://doi.org/10.34105/j.kmel.2014.06.030
Number: 4 KerkoCite.ItemAlsoKnownAs: 2339240:PDQV4A7I 2405685:LCDRVZPJ
Keywords: ⛔ No DOI found

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
ZenodoArchiveID: 7139243 ZenodoArchiveConcept: 7139242 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7139243 10.53832/edtechhub.0122 2405685:Z8B66R9X
Keywords: _r:AddedByZotZen

Low cost tablet enhanced pedagogy for early grade reading: Indian context - Nedungadi, Prema; Jayakumar, Akshay; Raman, Raghu (2014 IEEE Region 10 Humanitarian Technology Conference (R10 HTC), 2014)
In our research we have designed pedagogy for Low Cost Tablets (LCT) to enhance early grade reading in multigrade classrooms in rural areas of India. The use of LCT helps meet the challenge of education in areas where there is a lack of qualified tutors and shortage of computing resources. The program has been implemented with (N=38) students in tribal areas of Kerala. Reading was the most common problem with the primary children, while mathematics and reading comprehension was a major challenge for children who were in middle school. Our pilot study students were able to learn faster on their own without requiring formal training due to the ease of use and the touch based interface of LCT, and they liked the idea of repeating lessons as many times as they wished. Teachers were trained in the use of LCT for assessment and early intervention and effective ways to bring up the reading skills of the students. Our findings confirm that LCT is powerful motivator in education and has a huge potential to address the issue of school dropouts. Our proposed pedagogy for LCT and findings will be of interest to educational policy makers who are looking at LCT options such as Aakash tablets to improve literacy levels among early grade learners.
KerkoCite.ItemAlsoKnownAs: 10.1109/R10-HTC.2014.7026322 2339240:52QRVY4T 2405685:A64MD23Q

The Challenge of Education and Learning in the Developing World - Kremer, Michael; Brennen, Conner; Glennerster, Rachel (Science, 2013)
Across many different contexts, randomized evaluations find that school participation is sensitive to costs: Reducing out-of-pocket costs, merit scholarships, and conditional cash transfers all increase schooling. Addressing child health and providing information on how earnings rise with education can increase schooling even more cost-effectively. However, among those in school, test scores are remarkably low and unresponsive to more-of-the-same inputs, such as hiring additional teachers, buying more textbooks, or providing flexible grants. In contrast, pedagogical reforms that match teaching to students' learning levels are highly cost effective at increasing learning, as are reforms that improve accountability and incentives, such as local hiring of teachers on short-term contracts. Technology could potentially improve pedagogy and accountability. Improving pre-and postprimary education are major future challenges.
Publisher: American Association for the Advancement of Science KerkoCite.ItemAlsoKnownAs: 10.1126/science.1235350 2339240:67BCHX95 2339240:MUEFL3NF 2405685:PFYKPNHQ 2405685:U4T6SC5D
Keywords: ___working_potential_duplicate

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Effective and scalable math support: Experimental evidence on the impact of an AI-math tutor in Ghana (Communications in Computer and Information Science, 2024)
This study is a preliminary evaluation of the impact of receiving extra math instruction provided by Rori, an AI-powered math tutor accessible via WhatsApp, on the math performance of approximately 500 students in Ghana. Students assigned to both the control and treatment groups continued their normal classes with identical curricula and classroom hours. Students in the treatment group were given access to a phone for one hour a week – during their study hall period – and were allowed to use Rori to independently study math. All other aspects of the groups’ in-school experience were the same. We find that the math growth scores were substantially higher for the treatment group and statistically significant (p < 0.001). The effect size of 0.36 is considered large in the context of educational interventions: approximately equivalent to an extra year of learning. Importantly, Rori works on basic mobile devices connected to low-bandwidth data networks, and the marginal cost of providing Rori is approximately $5 per student, making it a potentially scalable intervention in the context of LMICs’ education systems. While the results should be interpreted judiciously, as they only report on year 1 of the intervention, they do suggest that chat-based tutoring solutions leveraging AI could offer a cost-effective and operationally efficient approach to enhancing learning outcomes for millions of students globally.
ISSN: 1865-0929, 1865-0937 KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-64315-6_34 2339240:23TJHX6S 2405685:L7WVWEPE

The True Cost of Freemium - Ferry, Anna (CPO Magazine, 2018)
Section: Data Privacy KerkoCite.ItemAlsoKnownAs: 2339240:IUSPGZNA 2405685:RR5WASM6

SmartIT: Total Cost of Ownership Assessment - Consortium for School Networking (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:JD9MQENJ 2405685:FVTSMWDW

Template for costing remote learning encouragement - Blagrave, Holly Jean (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:WVNZ95F5 2405685:NMXS89SP

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
previousshortDOI: 10/ghgk6r previousDOI: 10.5281/zenodo.3884302 EdTechHub.Source: 2405685:6W2UWE89 EdTechHub.Source: <this> shortDOI: 10/ghgk6r KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 10.53832/edtechhub.0041 10/ghgk6r 2129771:2MD2QL8K 2339240:7QEJ68RG 2405685:6W2UWE89 2405685:7HQN2HAD
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

Capturing Cost Data - World Bank; International Rescue Committee (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:IJ5E95SQ 2405685:4DU2PHIC 2405685:ZSZN39Y5
Keywords: ⛔ No DOI found

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1844782 2339240:ZWKGJ4FV 2405685:YPU8GIXB

Moving towards cost-effective delivery models of teacher coaching: evidence from field experiments in South Africa - Kotze, Janeli; Taylor, Stephen; Fleisch, Brahm (2018)
Structured learning programmes have emerged as a promising way to address the low learning levels observed in many developing countries. The delivery model of these programmes matters, and on-site teacher coaching has been recommended to be highly effective, especially in early grade literacy. In this paper, we report on a series of government-led randomised experiments in South African primary schools that build on each other to test various models of teacher training and coaching. We find that sustained on-site coaching is more cost-effective (0.41 SD increase in test scores per USD 100) than either short coaching interventions (no significant impact) or centralized teacher training workshops (0.23 SD increase in test scores per USD 100). The ability to scale on-site coaching, however, is an open question. In the latest experiment, therefore, a virtual coaching programme was compared to on-site coaching. The focus of this paper is on the midline evaluation results from this experiment. After one year of intervention, virtual coaching was no less effective than on-site coaching at improving both the instructional practice of teachers and the targeted literacy outcomes of children. This points to the potential for technological innovations to enable wider rollout of coaching programmes, even in contexts where teachers are not familiar with new technologies.
KerkoCite.ItemAlsoKnownAs: 2339240:A58ENCQR 2339240:MC3TURVW 2405685:6RASPKEH 2405685:72SDEPAH 2405685:PLJ4WN63 2534378:4AZ7VHMD 2534378:U88KUB3W
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425920; __finaldtb; ⛔ No DOI found

Cost Measurement Guidance Note for Donor-Funded Education Programming - Walls, Elena; Tulloch, Caitlin; Holla, Alaka (United States Agency for International Development, prepared for Building Evidence in Education (BE2), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CWNWAYRP 2405685:S33RE2WF

Supporting Parenting through Differentiated and Personalized Text-Messaging: Testing Effects on Learning During Kindergarten - Doss, Christopher; Fahle, Erin; Loeb, Susanna; York, Ben (2017)
Recent studies have shown that texting-based interventions can produce educational benefits in children across a range of ages. These studies vary in their focus from broad curricula on child development, to reminders about missing work, to steps needed in order to enroll in college. Given the potential effectiveness of texting, as well as the ease of systematically varying
KerkoCite.ItemAlsoKnownAs: 2339240:9AKV6UFP 2405685:RWQG2ZYP 2405685:WL2K529Q
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Cost Analysis Guidance for USAID-Funded Education Activities - Walls, Elena; Tulloch, Caitlin; Harris-Van Keuren, Christine (United States Agency for International Development, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:B3MXXXAW 2405685:GJU2GCWA

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13116 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 2339240:7C7I9C4I 2405685:4MGG3JS3
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

Texting Parents about Early Child Development: Behavioral Changes and Unintended Social Effects - Barrera, Oscar; Macours, Karen; Premand, Patrick; Vakis, Renos (The World Bank, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-9492 2339240:R5IIXYTZ 2405685:JYCH7N3U

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

Education sector analysis methodological guidelines - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2014)
The Methodological Guidelines provide methods for carrying out a comprehensive analysis of the education sector in developing countries. Volume 1 of the guidelines discusses the context for the development of the education sector, enrollment, internal efficiency, out-of-school children, cost and financing, quality, system capacity and management, external efficiency and equity.
KerkoCite.ItemAlsoKnownAs: 2339240:JEZ8LW9X 2339240:R2HMFCUX 2405685:24DM6GFV 2405685:HCLG4ULQ

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5654887 10.53832/edtechhub.0067 2339240:VNTPMCJQ 2339240:XLHSGBDA 2405685:FSVST5BF 2405685:HVDCZZVG 2405685:L5WPA5SN 2405685:YWENAQDF
Keywords: _r:AddedByZotZen

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
ZenodoArchiveID: 3631748 previousshortDOI: 10/ghgngh previousshortDOI: 10/ghgngh previousDOI: 10.5281/zenodo.3631748 previousshortDOI: 10/ghgngh EdTechHub.Copy: 2129771:UEUAKMXJ EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngh KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631748 10.53832/edtechhub.0012 10/ghgngh 2129771:UEUAKMXJ 2339240:94ZP3EK4 2339240:E62J77SP 2339240:MM2SDXUM 2339240:S4UAH7Q3 2405685:3AV6MSKJ 2405685:DQWJLRN5 2405685:H9W2X3KM
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.
KerkoCite.ItemAlsoKnownAs: 2405685:XPZGL85X

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Isolating the “Tech” from EdTech: Experimental Evidence on Computer Assisted Learning in China - Ma, Yue; Fairlie, Robert; Loyalka, Prashant; Rozelle, Scott (National Bureau of Economic Research, 2020)
EdTech which includes online education, computer assisted learning (CAL), and remote instruction was expanding rapidly even before the current full-scale substitution for in-person learning at all levels of education around the world because of the coronavirus pandemic. Studies of CAL interventions have consistently found large positive effects, bolstering arguments for the widespread use of EdTech. However CAL programs, often held after school, provide not only computer-based instruction, but often additional non-technology based inputs such as more time on learning and instructional support by facilitators. In this paper, we develop a theoretical model to carefully explore the possible channels by which CAL programs might affect academic outcomes among schoolchildren. We isolate and test the technology-based effects of CAL and additional parameters from the theoretical model, by designing a novel multi-treatment field experiment with more than four thousand schoolchildren in rural China. Although we find evidence of positive overall CAL program effects on academic outcomes, when we isolate the technology-based effect of CAL (over and above traditional pencil-and-paper learning) we generally find small to null effects. Our empirical results suggest that, at times, the “Tech” in EdTech may have relatively small effects on academic outcomes, which has important implications for the continued, rapid expansion of technologies such as CAL throughout the world.
KerkoCite.ItemAlsoKnownAs: 10.3386/w26953 2339240:TNXB4CGW 2405685:K9L5U52U

Consolidated Feedback on Tanzania Higher Education University Strategic Investment Plans - Adam, Taskeen; Koomar, Saalim; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk Response provides feedback on 15 Tanzania University Strategic Implementation Plans (USIPs) submitted to the Word Bank’s Higher Education for Economic Transformation Project (HEET). The feedback is intended to enhance and strengthen the plans provided by universities such that the USD 300 million is allocated and spent most effectively.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3986727 2129771:B5Z854HJ 2339240:IEATEWRY 2405685:7AFXFRPC
Keywords: Helpdesk Response; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; dode_eth-src-eth; dode_eth-trf2-dode

Impact of Internet Access on Student Learning in Peruvian Schools - Kho, Kevin; Lakdawala, Leah; Nakasone, Eduardo (Michigan State University, Department of Economics, 2018)
We investigate the impacts of school-based internet access on pupil achievement in Peru, using a large panel of 5,903 public primary schools that gained internet connections during 2007-2014. We employ an event study approach and a trend break analysis that exploit variation in the timing of internet roll-out up to 5 years after installation. We find that internet access has a moderate, positive short-run impact on school-average standardized math scores, but importantly that this effect grows over time. We provide evidence that schools require time to adapt to internet access by hiring teachers with computer training and that this process is not immediate. These dynamics highlight the need for complementary investments to fully exploit new technological inputs and underscores the importance of using an extended evaluation window to allow the effects of school-based internet on learning to materialize.
Publication Title: Working Papers KerkoCite.ItemAlsoKnownAs: 2339240:7URC6DBK 2405685:SHDUYVBY
Keywords: Education; ICT; Internet; Schooling

Can One Laptop Per Child Save the World's Poor? - Warschauer, Mark; Ames, Morgan (Journal of International Affairs, 2010)
The One Laptop per Child (OLPC) program is one of the most ambitious educational reform initiatives the world has ever seen. The program has developed a radically new low-cost laptop computer and aggressively promoted its plans to put the computer in the hands of hundreds of millions of children around the world, including in the most impoverished nations. Though fewer than 2 million of OLPC's XO computers have been distributed as of this writing, the initiative has caught the attention of world leaders, influenced developments in the global computer industry and sparked controversy and debate about the best way to improve the lot of the world's poor. With six years having passed since Nicholas Negroponte first unveiled the idea, this paper appraises the program's progress and impact and, in so doing, takes a fresh look at OLPC's assumptions. The paper reviews the theoretical underpinnings of OLPC, analyzes the program's development and summarizes the current state of OLPC deployments around the world. The analysis reveals that provision of individual laptops is a utopian vision for the children in the poorest countries, whose educational and social futures could be more effectively improved if the same investments were instead made on more sustainable and proven interventions. Middle- and high-income countries may have a stronger rationale for providing individual laptops to children, but will still want to eschew OLPC's technocentric vision. In summary, OLPC represents the latest in a long line of technologically utopian development schemes that have unsuccessfully attempted to solve complex social problems with overly simplistic solutions.
Publisher: Journal of International Affairs Editorial Board KerkoCite.ItemAlsoKnownAs: 2339240:GXQVYARZ 2405685:9BRCRSSN 2405685:PUTV3LIS
Keywords: ⛔ No DOI found

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
previousshortDOI: 10/ghgngg previousshortDOI: 10/ghgngg previousDOI: 10.5281/zenodo.3631746 previousshortDOI: 10/ghgngg EdTechHub.Copy: 2129771:EHFUXJQC EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngg KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631746 10.53832/edtechhub.0011 10/ghgngg 2129771:EHFUXJQC 2129771:YHNWVMB3 2339240:94ZP3EK4 2339240:FIDI5TC2 2405685:39DIRNE9 2405685:HH3QKBIF 2405685:I3BV48CX 2405685:ITL9PIC3 2405685:K8BSWYFM 2405685:KF9F48ID 2405685:N68MMAPR 2405685:P5Y5GMFN 2405685:SC5NHA65 2486141:TAY7LNB6
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:BMZ8MTPR 2405685:GTZBXLQU
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
KerkoCite.ItemAlsoKnownAs: 2339240:Z7WED3QU 2405685:L6EEZ9LR
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14051241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1068 ZenodoArchiveConcept: 14051240
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Guidance Note 5 Supporting the effective use of digital technologies for learning by refugees and displaced persons From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684319 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684319 2339240:L97RQZU7 2405685:XUE9KMII
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
previousshortDOI: 10/ghgngk previousshortDOI: 10/ghgngk previousDOI: 10.5281/zenodo.3631750 previousshortDOI: 10/ghgngk EdTechHub.Copy: 2129771:5EWDQDIA EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngk KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631750 10.53832/edtechhub.0013 10/ghgngk 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:978RP7D4 2405685:VM6NXYF3
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2020)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64SDs and writing scores by 0.45SDs. A reduced-cost version instead yields statistically-insignificant reading gains and some large negative effects (-0.33SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
Publisher: MIT Press shortDOI: 10/gg7spz KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 10/gg7spz 2339240:VK3937E2 2405685:9UT2Q56S 2405685:EXQV8YBV 2447227:VDYKWJTR
Keywords: NULP; ___working_potential_duplicate

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

Making the grade: The sensitivity of education program effectiveness to input choices and outcome measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 10/gf6298 2339240:3W37ZTWQ 2405685:ME5VHAM9
Keywords: ___working_potential_duplicate

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694602 ZenodoArchiveConcept: 10694601 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080734 10.53832/edtechhub.1015
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effective Technology Approaches to Improve Education Outcomes for Girls: Learning from 41 Girls’ Education Challenge projects - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596887 ZenodoArchiveConcept: 5596886 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0060 2405685:8ZWX2JI5

The Use and Misuse of Computers in Education: Evidence from a Randomized Controlled Trial of a Language Arts Program - Barrera-Osorio, Felipe; Linden, Leigh L (2009)
This paper presents the evaluation of the program Computers for Education. The program aims to integrate computers, donated by the private sector, into the teaching of language in public schools. The authors conduct a two-year randomized evaluation of the program using a sample of 97 schools and 5,201 children. Overall, the program seems to have had little effect on students’ test scores and other outcomes. These results are consistent across grade levels, subjects, and gender. The main reason for these results seems to be the failure to incorporate the computers into the educational process. Although the program increased the number of computers in the treatment schools and provided training to the teachers on how to use the computers in their classrooms, surveys of both teachers and students suggest that teachers did not incorporate the computers into their curriculum.
KerkoCite.ItemAlsoKnownAs: 2339240:2B5GGTLG 2339240:9GDU893D 2405685:EJCKQUGC 2405685:PWS6BFPA
Keywords: ⛔ No DOI found

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

QALY-based cost-effectiveness analysis - Pinto-Prades, J. L; Herrero, C; Abellán, J. M (The Oxford Handbook of Well-Being and Public Policy, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:XLRKBCZ4

Cost-Effective Approaches to Improve Global Learning - Global Education Evidence Advisory Panel (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:URLC9S2L 2486141:9A53JU2Q

Achieving Cost-Effective Instructional Coaching at Scale: Evidence from Senegal - Bagby, Emilie; Swift-Morgan, Jennifer; Niang, Ablaye; Upadhyay, Arjun (Chemonics International, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:8AWEL33Y 2405685:7A7UIMZX

Outcomes-based funding in education: Assessing cost effectiveness and accountability - Government Outcomes Lab (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:NWAG5XDZ 2405685:7A5Y6H6T

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13766685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1059 ZenodoArchiveConcept: 13766684
Keywords: _r:AddedByMyEducationEvidence

One step at a time: the effects of an early literacy text-messaging program for parents of preschoolers - York, Benjamin N.; Loeb, Susanna; Doss, Christopher (Journal of Human Resources, 2019)
Large systematic differences in young children’s home learning experiences have long-term economic consequences. Many parenting programs place significant demands on parents’ time and inundate parents with information. This study evaluates the effects of READY4K!, an eight-month-long text-messaging intervention for parents of preschoolers that targets the behavioral barriers to engaged parenting. We find that READY4K! increased parental involvement at home and school by 0.15 to 0.29 standard deviations, leading to child gains in early literacy of about 0.11 standard deviations. The results point to the salience of behavioral barriers to parenting and the potential for low-cost interventions to reduce these barriers.
Publisher: University of Wisconsin Press KerkoCite.ItemAlsoKnownAs: 10.3368/jhr.54.3.0517-8756R 2405685:UV7WIAIX
Keywords: C93; D91; I21

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707940 2339240:PAIL2F6F 2405685:27J8ETI9 2405685:G34FUWKA
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Through the looking glass: can classroom observation and coaching improve teacher performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (Economics of Education Review, 2018)
We conducted a randomized evaluation of a program in Brazil that provided secondary schools with classroom observation feedback and access to expert coaching. Coaching content was based on Teach Like A Champion, by Douglas Lemov, which imparts practical strategies to increase teachers’ effectiveness by maximizing time on instruction and student engagement. In treatment schools, the program raised the skills of pedagogical coordinators tasked with supporting teachers to improve instruction, increased teachers’ time on instruction, raised student engagement and produced statistically significant student learning gains. Program schools performed 0.05–0.09 SD higher in 10th grade math and Portuguese on a state test and 0.06 SD higher in Portuguese on a national high school leaving test (12th grade). High quality coaching delivered to the coordinators via Skype kept costs at $2.40 per student, making the program a cost-effective and promising strategy for school-based efforts to raise teachers’ classroom effectiveness. (I21, I25, I28, J18, O15)
Extra URL: http://www.sciencedirect.com/science/article/pii/S0272775717303576 KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2018.03.003 10/ggft3x 2129771:PXEQ493U 2339240:EJ9DHWVT 2339240:TJCEV7VS 2405685:27VSFIJU 2405685:7A2ZCMGH 2405685:PH86GT2T 2534378:CH4WAJDT 2534378:FM4VRQ7G 2534378:X3NNFD6B
Keywords: Classroom observation; Economic development; Economic impact; Educational economics; Randomization; Teacher coaching; __:import:01; __:match:final; __:matched; __:study_id:2425900; ___working_potential_duplicate; __finaldtb

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
ZenodoArchiveID: 10529049 KerkoCite.ItemAlsoKnownAs: 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 10.53832/edtechhub.1003 ZenodoArchiveConcept: 10529048
Keywords: _r:AddedByMyEducationEvidence

Are contract teachers and para-teachers a cost-effective intervention to address teacher shortage and improve learning outcomes? - Kingdon, Geeta Gandhi; Aslam, Monazza; Rawal, Shenila; Das, Sushmita (Evidence for Policy and Practice Information and Co-ordinating Centre:Social Science Research Unit, Institute of Education, University of London, 2013)
OCLC: 1064447467 KerkoCite.ItemAlsoKnownAs: 2339240:KLB5ET5M 2405685:DIMSNBTN

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Abstract Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
_eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13116 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 2339240:6HPRIAVP 2405685:6UZHTZ8G
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

Stemming learning loss during the pandemic: A rapid randomized trial of a low-tech intervention in Botswana - Angrist, Noam; Bergman, Peter; Brewster, Caton; Matsheng, Moitshepi (SSRN Electronic Journal, 2020)
The COVID-19 pandemic has closed schools for over 1.6 billion children, with potentially long-term consequences. This paper provides some of the ﬁrst experimental evidence on strategies to minimize the fallout of the pandemic on education outcomes. We evaluate two low-technology interventions to substitute schooling during this period: SMS text messages and direct phone calls. We conduct a rapid trial in Botswana to inform real-time policy responses collecting data at four- to six-week intervals. We present results from the ﬁrst wave. We ﬁnd early evidence that both interventions result in cost-eﬀective learning gains of 0.16 to 0.29 standard deviations. This translates to a reduction in innumeracy of up to 52 percent. We ﬁnd increased parental engagement in their child’s education and more accurate parent perceptions of their child’s learning. In a second wave of the trial, we provide targeted instruction, customizing text messages to the child's learning level using data from the ﬁrst wave. The low-tech interventions tested have immediate policy relevance and could have long-run implications for the role of technology and parents as substitutes or complements to the traditional education system.
shortDOI: 10/ghd7tq KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3663098 10/ghd7tq 2129771:37WVYGRH 2129771:3GGG8ENA 2129771:4XBSBHNZ 2129771:NQQA5HAW 2129771:ZAKRMJ4F 2339240:2WJEWLAA 2339240:3KEMQZFY 2339240:8UQPKQ7W 2339240:A6GTDZPI 2339240:S9NW6UM3 2339240:TUIKVLFK 2339240:WELWFJX5 2405685:7YTYUC4P 2405685:CI9DR8FZ 2405685:FVE4BJUX 2405685:LH88EXET 2405685:RL286U4T 2405685:SE6BFJGL 2405685:VDBNW37T 2405685:XRR4DFUM
Keywords: Education; Human Capital; Technology; _COVID_DEAA-List; __C:filed:1; ___working_potential_duplicate

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

COVID-19 is a serious threat to aid to education recovery | Global Education Monitoring Report - UNESCO (UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:8PMPRXLC 2405685:EMKE5928

Do School Electriﬁcation and Provision of Digital Media Deliver Educational Beneﬁts? First-year Evidence from 164 Tanzanian Secondary Schools - Seo, Hee Kwon (University of Chicago, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:9XWPHF2H 2405685:DPI4T7LU

Global EdTech market to reach $404B by 2025 - 16.3% CAGR. - HolonIQ (HolonIQ, 2020)
Section: K12 KerkoCite.ItemAlsoKnownAs: 2339240:3E7YSFAR 2405685:IQMVRCQ6

Expenditures and Revenue Management - Morrell, Lance (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:LW7XXDQC 2405685:LIVD2ABR

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-13-1414-8_8 2339240:22I8PCDJ 2405685:8FWZU7FX
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

Multi-Sectoral Rapid Needs Assessment: COVID19 - Jordan - UNHCR; UNICEF; WFP (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:U34LB7JG 2405685:BWEZPV5L

Opportunities for Equitable Access to Quality Basic Education (OPEQ): Final Report on the Impact of the OPEQ Intervention in the Democratic Republic of Congo - Aber, J. Lawrence; Starkey, Leighann; Tubbs, Carly; Torrente, Catalina; Johnston, Brian; Wolf, Sharon; Shivshanker, Anjuli; Annan, Jeannie (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:ABHT5QJ4 2405685:38QVMKG5

Ready4K - ParentPowered (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:HGUC9MU7 2405685:V6PFRQLX

SDG7: Data and Projections - International Energy Agency (IEA, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:HSXM7FSQ 2405685:YMEW7GGP

The difference between economic and financial analysis for WASH services - Ross, Ian (WASHeconomics.com, 2018)
The distinction between economic analysis and financial analysis is not always straightforward. In this post I try to clarify this. Definitions I have previously defined WASH economics as “the stud…
KerkoCite.ItemAlsoKnownAs: 2339240:RI9C4FHT 2405685:QWR4ZRBS

Value for Money Policy and Procedure - EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:DLHKFUVC 2405685:V6TUMYRQ

Value for money and international development: Deconstructing myths to promote a more constructive discussion - Jackson, Penny (OECD Development Co-operation Directorate, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:TPBV4E5D 2405685:8ILRQE95

Virtual Roundtable on Structured Pedagogy - better purpose (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:9FRXYLAQ 2405685:3P77F7IB

World Development Indicators - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:76GX39L8 2405685:2QBLXZAJ

Promoting academic literacy with technology: successful laptop programs in K-12 schools - Warschauer, Mark; Grant, David; Real, Gabriel Del; Rousseau, Michele (System, 2004)
One of the main challenges that US schools face in educating English language learners is developing their academic literacy. This paper presents case studies of two K-12 schools that successfully employ high-technology environments, including laptop computers for each student, toward the development of English language learners’ academic language proficiency and academic literacy. In the first school, Latino fourth-grade students use laptops and other new technologies for a wide variety of pre- and post-reading tasks as part of their effort to transition from learning to read to reading to learn. In the second school, diverse immigrant and refugee students at the middle school level combine technology use with Expeditionary Learning to carry out community projects leading to the development of sophisticated products. In both schools, technology is used to engage students in cognitively demanding activity, motivate independent reading, and provide scaffolding for language development, while the researchers also made use of technology to document learning processes and outcomes. Taken together, the schools offer valuable lessons for utilization of technology to promote academic literacy among culturally and linguistically diverse students.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.system.2004.09.010 10/ffr68w 2339240:CR5JUUTC 2405685:9TQ7P4IC
Keywords: Laptops; Literacy; Technology

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2339240:EYQWGP5R 2405685:ZGFQHAS3

How ed-tech can help leapfrog progress in education - Vegas, Emiliana; Ziegler, Lauren; Zerbino, Nicolas (Brookings, 2019)
This brief analyzes the use of ed-tech innovations around the world.
KerkoCite.ItemAlsoKnownAs: 2339240:LH87HU6C 2405685:D9VNFXR8

Education Finance Watch 2021 - World Bank; UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IH8UXUCR 2405685:QQ5SXSCG

onetab - onebillion (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:63XVIAX4 2405685:II2Z2MLN

Unlocking Talent - Unlocking Talent (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VGLYSWAB 2405685:7RUAVAA4

Research - EdTech Hub (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S7VNMT74 2405685:SGN72ZXM

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Teacher professional development in sub-Saharan Africa: Equity and scale - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (Embedding Social Justice in Teacher Education and Development in Africa, 2021)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
KerkoCite.ItemAlsoKnownAs: 2129771:E2Q73NBN 2129771:EPYMVB2W 2405685:SM8RY6F9
Keywords: Author:Haßler; Björn-CV-OECS; _yl:a; dode_eth-src-dode; dode_eth-trf2-dode

What are the impacts and cost effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries? Protocol - Pryor, John; Westbrook, Jo; Adu-Yeboah, Christine; Orr, David; Durrani, Naureen (EPPI-Centre, Social Science Research Unit, Institute of Education, University of London, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:AXK7CQ2A 2405685:NG2DIRTE

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6337916 10.5281/zenodo.6337918 10.5281/zenodo.6338002 10.5281/zenodo.6338007 10.53832/edtechhub.0083 2339240:AZXVF44M 2339240:GZRZGRN7 2339240:MJPJVVCU 2405685:6QCZIQR2 2405685:D9VW8AI3 2405685:PWU63GQS 2405685:QAXG3NCJ 2405685:RKRPWPX5 2405685:VT5Z6XB6 2405685:YBG8MTTQ 2405685:ZDHGEBKD
Keywords: _r:AddedByZotZen

2023 Cost-Effective Approaches to Improve Global Learning: What does recent evidence tell us are "Smart Buys" for improving learning in low- and middle-income countries? - Akeyampong, K; Andrabi, T; Banerjee, A; Banerji, R; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Ruto, S; Saavedra, J; Schmelkes, S; et al. (World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:F52H6KKX 2405685:NP2EKHJP 2405685:V968A8F8 2486141:PEQB9DK3
Keywords: ⛔ No INSPIRE recid found

2023 Cost-Effective Approaches to Improve Global Learning - What does recent evidence tell us are “Smart Buys” for improving learning in low- and middle-income countries? - Banerjee, A; Banerji, R; Andrabi, T; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Saavedra, J; Yoshikawa, H; Ruto, S; Schmelkes, S (World Bank Group, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2BGTWZKU 2339240:X7GEK8EA 2405685:9X68BZ9M 2405685:J3TLG7EN 2405685:XW55C644

Scaling Access & Impact: Realizing the Power of EdTech - Pouezevara, Sarah; Valdivia, Ignacio Jara; Michalec, Mike; Amalia, Talitha; Fleischmann, Sybille (Omidyar Network, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GZZQHMNZ 2405685:CAXD8U9H

The rise and fall of the PC in one chart - Booton, Jennifer (MarketWatch, 2016)
Section: Industries KerkoCite.ItemAlsoKnownAs: 2339240:USFBBPHB 2405685:D94GQ9W9

Does Education Need a QALY and Is LAYS It? - Crawfurd, Lee; Hares, Susannah; Le Nestour, Alexis; Rossiter, Jack (Center For Global Development, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HEH7E87J 2405685:YR4DSMZM

Two-Thirds of Poorer Countries Are Cutting Education Budgets Due to COVID-19 - World Bank (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GK2Z7TZH 2405685:HJF56BG6

COVID-19 and options for financing education - Read, Lindsay (Save Our Future, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:E9UXAI3F 2405685:EWQEBEM5

Jusoor’s WhatsApp-Assisted Learning Programme: Sprint Review 1. - Tutunji, Suha; Boujikian, Michèle; Carter, Alice; Atkinson, Grace (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:G5RD3H5K 2405685:NBWSSFLK
Keywords: ___working_potential_duplicate

Reimagine Education – Summary Case for Investment - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:F2TZJVCY 2339240:PZUV47J2 2339240:XCF84QXK 2405685:ILKQWGXN 2405685:VRYJIY4N 2405685:XFYKJDMJ

Global Dataset on Education Quality : A Review and Update (2000-2017) - Patrinos, Harry Anthony; Angrist, Noam (World Bank Group, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:IB5T4GSH 2405685:MCNGDVIH

EdTech in Indonesia: Ready for Take-off? - Bhardwaj, Riaz; Yarrow, Noah; Calì, Massimiliano (World Bank Group, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4B3EHJHR 2405685:LZVIGAX3

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
ZenodoArchiveID: 5652141 previousDOI: 10.5281/zenodo.4762283 previousDOI: 10.5281/zenodo.4762283 2405685:UQSMRFBF previousDOI: 10.5281/zenodo.3407498 EdTechHub.Source: DOI: DOI:10.5281/zenodo.4762283 2405685:UQSMRFBF EdTechHub.Source: <this> shortDOI: 10/ghgnd8 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407498 10.5281/zenodo.5652141 10/ghgnd8 2129771:U3XSZB5F 2339240:CRCGCNE9 2405685:UQSMRFBF
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Publisher: University of the West Indies KerkoCite.ItemAlsoKnownAs: 2339240:A3WF6P6D 2339240:KUAK4YAL 2339240:XJJARH42 2405685:8H75L794 2405685:PB6US4IE 2405685:U97W3BR2
Keywords: ⛔ No DOI found

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Makhalidwe Athu - Creative Association International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6C5I8Z2D 2405685:KDTFJ3QR

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CV6J6IEN 2405685:Q6H4DRVL

Makhalidwe Athu - Creative Association International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6C5I8Z2D 2405685:KDTFJ3QR

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, 2020)
Education for the most marginalised post‑COVID-19 Guidance for governments on the use of digital technologies in education Join us December 18 for the report launch! Click here to register. The UNESCO Chair in ICT for Development, with support from the EdTech Hub, developed this report and associated Guidance Notes in 2020 building on a series of regional and sectoral consultations…
KerkoCite.ItemAlsoKnownAs: 2339240:IK5SDRGN 2339240:JTDGHA3K 2405685:D22ZXDPG 2405685:UNZYXGC6
Keywords: ___working_potential_duplicate

Save our future - Haßler, Björn; Sagun, Rose (2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749380 2405685:QLTPHU6B
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodoODE

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (2020)
Presentation given at BE2, 2020-10-06.
shortDOI: 10/ghgnf4 KerkoCite.ItemAlsoKnownAs: 10/ghgnf4 2129771:WPJL8SN3 2339240:7TXCEBE6 2405685:5VQMVDB9
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobilephones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
KerkoCite.ItemAlsoKnownAs: 2405685:VLPHGQ5H
Keywords: C:Bangladesh

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
shortDOI: 10/ggtsmj KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 10/ggtsmj 2339240:DKVPCJ4N 2405685:EBIDU596 2405685:EHX857GT
Keywords: C: Ghana

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341509 ZenodoArchiveConcept: 7341508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341509 10.53832/edtechhub.0139 2405685:NUTI6KUS 2405685:PPRW2NTQ
Keywords: _r:AddedByZotZen

Sandboxes: our approach to systemic experimentation - Simpson, Lea (EdTech Hub, 2020)
What’s a sandbox you ask? First in the series, this blog explains what you need to know about the Hub’s approach to experimentation and innovation.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:N8IVIWTD 2339240:UM8QDJVD 2405685:EU5H44PP 2405685:T22QNFKK 2405685:XZLUI8BE
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Through the Looking Glass: Can Classroom Observation and Coaching Improve Teacher Performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (World Bank Group, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:GTWNV6MT 2405685:U2D68PYR
Keywords: ___working_potential_duplicate

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6981598 ZenodoArchiveConcept: 6981597 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6981598 10.53832/edtechhub.0105 2405685:BDT76583
Keywords: _r:AddedByZotZen

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Learning-Adjusted Years of Schooling (LAYS): Defining A New Macro Measure of Education - Filmer, Deon; Rogers, Halsey; Angrist, Noam; Sabarwal, Shwetlena (World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8591 2339240:3A9F6FVB 2339240:KGVQPHCJ 2405685:59ERQXRR 2405685:GSG23QSA 2405685:TP9IZVSC 2447227:6BFXZ6TA 2561267:ELKQGNZN
Keywords: _B:important; ___working_potential_duplicate; _final_bib; _important; _s:DFID; ⛔ No DOI found; ❓ Multiple DOI

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Use of digital game based learning and gamification in secondary school science: The effect on student engagement, learning and gender difference - Khan, Amna; Ahmad, Farzana Hayat; Malik, Muhammad Muddassir (Education and Information Technologies, 2017)
This study aimed to identify the impact of a game based learning (GBL) application using computer technologies on student engagement in secondary school science classrooms. The literature reveals that conventional Science teaching techniques (teacher-centered lecture and teaching), which foster rote learning among students, are one of the major concerns in Pakistan Education system. This leads to student disengagement in science lessons eventually resulting in student absenteeism and dropouts from the schools. This study consisted of five stages: (1) examining the impact of Digital Game-Based Learning (DGBL) and gamification on engagement, learning and gender difference, and literature related to using DGBL models for instructional design; (2) planning learning activities and developing a GBL application based on a specific content in Science; (3) conducting an intervention with a sample of 72 participants of 8th grade (aged 12–15) in a low cost private school of Pakistan following quasi-experimental research framework; (4) observing behaviour and emotions of the participants during science lessons; (5) conducting pre and post tests to assess the learning outcomes of participants followed by focus groups discussion. Analysis from Friedman test, Mann-Whitney U test, and Wilcoxon Signed Rank test show that the GBL application has a positive influence on student engagement. However, GBL application was not equally effective for all students since girls outperformed boys in terms of engagement and learning outcomes. This study gives insights into the development of better educational games to promote student learning.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-017-9622-1 2339240:8MNNLVNL 2405685:629DUKTV

Improving educational quality with interactive radio instruction : a toolkit for policymakers and planners - Anzalone, Stephen; Bosch, Andrea (The World Bank, 2005)
This toolkit offers a timely compilation and analysis of recent experience of interactive radio instruction (IRI) in Africa and elsewhere. It explains the IRI concept. It guides the reader through the process of determining when IRI might be appropriate in a given context, and it describes the steps in setting up an IRI program. The authors emphasize the critical factors for success, including appropriate policy frameworks as well as planning for the necessary investment and sustainability. The report is organized as follows: Chapter 1 generally describes the IRI methodology and discusses the effectiveness, scale, and sustainability of the IRI approach. Chapter 2 then outlines steps for assessing the potential and appropriateness of IRI for improving educational quality in primary school classrooms in a given country, and chapter 3 leads the reader through a guided decision-making process for identifying the issues involved in applying the IRI methodology in particular country contexts. Two appendixes give summary data and illustrate, through brief vignettes, how IRI programs have worked in Sub-Saharan African countries. The Resources section contains further useful information, much of it available online.
KerkoCite.ItemAlsoKnownAs: 2339240:8QDN7BMS 2339240:K2FIBK5K 2339240:TLH2JJ3U 2339240:XNBYH9JL 2405685:58YH9N6Q 2405685:HYGP89Y7 2405685:RRYF7LNB 2405685:WXZ2G3I3 2405685:XN7X2G9L 2534379:8DIQB53I
Keywords: Commitment; ___working_potential_duplicate; broadcasting; cost

Inclusive Quality Education for Children with Disabilities - Singal, Nidhi; Ware, Hannah; Bhutani, Sweta Khanna (World Innovation Summit for Education & University of Cambridge, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:4ZA5WMI7 2339240:VS2APB8E 2339240:WALVDQHQ 2405685:B7XYHF4V 2405685:G784RVFY 2405685:UHVMVWIX

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 14 Partnerships with the private sector and civil society From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684345 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684345 2339240:ZD696VRL 2405685:EGYJSMZC 2405685:UW2H22R7
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

The global stakes of digitalization in education - Haßler, Björn (2021)
PreviousDOI: 10.5281/zenodo.4888604 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4888887 2405685:J49DGN5M
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
shortDOI: 10/gftr63 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2011.581014 10/gftr63 2339240:7KFNHLPK 2339240:I6BDIQNZ 2339240:JJ5GL8XB 2339240:LE5N7BCQ 2405685:CBBDLLFH 2405685:J57J3RGT 2405685:PDZKWSFZ 2405685:Q7GP9QSC 2405685:QWHDI7ZH 2534378:L9VFMLYK
Keywords: C:Kenya / Uganda / Tanzania; Education; Education for All; Education reform; Kenya; Pedagogy; Principles; Quality of education; Tanzania; Teacher education; Uganda; ___working_potential_duplicate; basic education; pre-service and in-service training; quality education; sub-Saharan Africa; teacher education reform

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

One Laptop per Child at home: Short-term impacts from a randomized experiment in Peru - Beuermann, Diether W.; Cristia, Julian; Cueto, Santiago; Malamud, Ofer; Cruz-Aguayo, Yyannu (American Economic Journal. Applied Economics, 2015)
This paper presents results from a randomized controlled trial whereby approximately 1,000 OLPC XO laptops were provided for home use to children attending primary schools in Lima, Peru. The intervention increased access and use of home computers, with some substitution away from computer use outside the home. Children randomized to receive laptops scored about 0.8 standard deviations higher in a test of XO proficiency but showed lower academic effort as reported by teachers. There were no impacts on academic achievement or cognitive skills as measured by the Raven's Progressive Matrices test. Finally, there was little evidence for spillovers within schools. (JEL I21, I28, J13, O15)
Num Pages: 28 Place: Nashville, United States Publisher: American Economic Association Section: Articles KerkoCite.ItemAlsoKnownAs: 10.1257/APP.20130267 10.1257/app.20130267 10/gd853r 2339240:27SMHV3H 2339240:CPRGCBM2 2339240:TELXF9WP 2405685:9EXLABVP 2405685:9FMQU6XN 2405685:XXVAITEK
Keywords: ACCESS TO LAPTOPS; Academic achievement; Achievement tests; Business And Economics; EXCLUSION CRITERIA APPLIED; Elementary school students; Portable computers; Quality: H; Relevance: M; Statistical analysis; ___working_potential_duplicate; publishPDF

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

Sustainability and interactive radio instruction: why some projects last - Bosch, Andrea (Adapting Technology for School Improvement A Global Perspective, 2004)
This book presents a compilation of articles based on the premise that the move to advanced technology use in primary and secondary schools offers great hope for improving the access, quality, and efficiency of basic education. The aim of the book is to identify and examine how information technologies can be, and are being, used to strengthen the quality of primary and secondary education. The articles take a global focus, drawing on examples from a wide range of countries. The book analyzes the challenges that teachers and educational planners face as they make this move, and shares how those challenges are being met in some of the countries now engaged in this effort. Several major themes are explored: the role of technology in school improvement, top-down versus bottom-up approaches, interactive radio instruction in schools, computers in the classroom, technology in teacher education, and adopting and implementing technology. The conclusions of the book examine strategies such as the cross-national sharing of curriculum development and instructional materials, and the training and support of teachers and administrators. The need for new partnerships, such as public-private and central-local, to make continued developments in technology sustainable, are also examined. The book divides into 14 chapters: (1) The Role of Technology in School Improvement (David W. Chapman, Amy Garrett, and Lars O. Mahlck); (2) Are New Technologies Better Technologies? For Whom? (Claudio de Moura Castro); (3) International Uses of Education Technology Threats and Opportunities (Stephen P. Heyneman and Katherine Taylor Haynes); (4) Using Instructional Technology as a Bridge to the Future: Palau's Story (Gregory C. Sales and Masa-Aki N. Emesiochl); (5) The Introduction of Computers in Secondary Schools in Jamaica: A Case of Bottom-Up Reform (Errol Miller); (6) Distance Education in Ethiopia (Teshome Nekatibeb and Thomas Tilson); (7) Sustainability and Interactive Radio Instruction: Why Some Projects Last (Andrea Bosch); (8) Is Constructivism Universal? In Search of Meaningful Technology in Morocco and Namibia (Jeffrey Coupe, Jeffrey Goveia, Houcine El Haichour, and Alfred Ilukena); (9) Technology and Educational Change at the Local Level: The Case of the Campana Schools Network in Argentina (Cecilia Braslavsky and Laura Fumagalli); (10) The Pedagogical Uses of Web-Based Chat: The Brazilian Experience (Vera Atsuko Suguri, Maria de Lourdes Matos, Noara M. de Resende e Castro, Rosal va Ieda V. Guimaraes de Castro, Lurdes Marilene da Silva Jung, and Eric Rusten); (11) Utilizing Technology in a Rural Teacher Certification Programme in Iceland (Ingolfur Asgeir Johannesson and Anna Thora Baldursdottir); (12) Integrating Technology into Education: The Czech Approach (Bozena Mannova); (13) The School Online Initiative in German Schools: Empirical Results and Recommendations to Improve School Development (Renate Schulz-Zander); and (14) Effective Use of Technology to Improve Education: Lessons for Planners (Lars O. Mahlck and David W. Chapman). This book is intended for educational policymakers, administrators, planners, and curriculum development specialists concerned with how technology can be used to extend access and raise the quality of education in their countries. It is also intended for international organizations, development assistance agencies and NGOs that are often most responsible for advocating the use of technology as a solution to education problems in low and middle-income countries. (Individual chapters contain references.).
OCLC: 1064923325 KerkoCite.ItemAlsoKnownAs: 2339240:83PCK5YZ 2405685:KKI68BXJ
Keywords: Commitment; Cost; content

How countries are using edtech (including online learning, radio, television, texting) to support access to remote learning during the COVID-19 pandemic - World Bank (World Bank, 2020)
Examples of how countries are using edtech to support remote learning under COVID-19
KerkoCite.ItemAlsoKnownAs: 2339240:32HB6XZZ 2339240:4BZJ4AIG 2339240:EX5BNITY 2339240:PBQ9WI2Z 2339240:WR9PK27B 2405685:57383Q46 2405685:773AJIR4 2405685:8HY8ZHY3 2405685:BAGXUAR8 2405685:RGLRHG75
Keywords: ___working_potential_duplicate

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 4 Inclusion and accessible learning for people with disabilities From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684317 2339240:LKN74WQK 2405685:56QA2K9Y
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Technology use for teacher professional development in low- and middle-Income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 10.5281/zenodo.4733147 2339240:5GVQGQC4 2339240:GQEBFNI2 2339240:LPFYJHUF 2339240:Q5369EBL 2405685:66IBMGWS 2405685:E5J2KHF2 2405685:KXGE9JIR 2405685:P4MI8J9M 2405685:R3SISS58 2405685:RKQI4W3A 2405685:T5QVE96Z 2534378:5CCARHUH 2534378:DZ4AXQJ2 4042040:V58GV3BA
Keywords: Disability; ICT; Read; Referenced; Teacher education and training; Teacher professional development; What works evidence; _EdTechHub_Output; _MELA_knowledge_product; _MELA_seen; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology; ⛔ No DOI found

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence

Monitoring and evaluation of the e-readers project in rural Tanzania - Machuve, D. Z.; Zlotnikova, I.; Nyambo, D. (Proceedings of the 2nd Pan African International Conference on Science, Computing and Telecommunications (PACT 2014), 2014)
This study provides recommendations on the monitoring and evaluation conducted for an ICT in Education project in two rural primary schools in Tanzania. The objective of the study was to evaluate the effectiveness of e-readers introduction at the schools. The e-readers introduction aimed at complementing the traditional print books. Print books are insufficient in primary schools in Tanzania; this ultimately leads to lack of reading skills in pupils and poor overall academic performance. As a conceptual framework the study adopted the InfoDev Monitoring and Evaluation framework for ICT in Education projects and adjusted it to local conditions. The study has shown that pupils at both schools considerably improved their reading skills as a result of the e-readers introduction. The introduction of e-readers also resulted in teachers and pupils being more motivated and engaged in learning. Survey results for parents demonstrate readiness on cost-sharing for acquiring the devices. This also indicates the feasibility of up-scaling the project to other schools in the country.
KerkoCite.ItemAlsoKnownAs: 10.1109/SCAT.2014.7055138 2339240:DPBJTXNM 2405685:HU86I3P7
Keywords: E-readers; Educational institutions; ICT; ICT in Education project; InfoDev Monitoring and Evaluation framework; Monitoring; Tanzania; academic performance; computer aided instruction; cost-sharing; digital e-books; e-readers project; electronic publishing; mobile computing; mobile electronic device; pupil engagement; pupil motivation; reading skills improvement; rural Tanzania; rural primary schools; teachers

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
ZenodoArchiveID: 3756012 previousDOI: 10.5281/zenodo.3756012 EdTechHub.Source: 2405685:JLEWADHF EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3756012 10.53832/edtechhub.0005 2129771:SB3DJ28L 2129771:XKGV4EYL 2339240:5FRH2GYG 2339240:97HNYI75 2339240:S82QHGKQ 2405685:JLEWADHF 2405685:JTYIWEJY 2405685:L8KCID8V 2405685:NLEUNMRZ 2405685:SCDLVVC7 2405685:YMZUYZ4Z 2486141:9MWJP6MS
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

School mapping and decision-making - Vijil-Morin, Alejandra; Godwin, Katie; Ramirez, Ana; Mackintosh, Alasdair; Haßler, Björn (GEM Report UNESCO, 2023)
Reliable and timely data is essential for decision-makers at all administrative levels to ensure inclusive, equitable, and quality education for all. Geospatial data has the potential to provide valuable insights across a range of areas of interest to the education sector, from identifying potential threats to schools and the education community, such as throughdata on natural disaster patterns, to supporting equitable allocation of resources based on data showing the remoteness of schools. However, the use of Geographic Information Systems (GIS) is not widespread in the education sector. In this paper, we shed light on the experiences of five country governments, one regional agency, one international initiative, one implementing partner and one private entity, all using GIS for education decision-making in Latin America, the Caribbean, and sub-Saharan Africa.This paper presents the findings from primary data collection and analysis of interviews with representatives from these organisations from August –December 2022. Across these countries, we identified two central applications of school geospatial data, which included education planning -which school mapping is a part of -and cross-sector coordination. Among the main challenges to effectively using school geospatial data to make decisions, we found significant issues with capacity building, funding, bridging the data, and policymaking. On the other hand, when school mapping was used effectively, it helped increase transparency and equity, intersectoral collaboration, cost-effectiveness, and accuracy and reliability. After comparing the seven cases, we concluded that two key enablers need to be in place to promote the impact of geospatial data on educational decision-making: ‘usability’ and ‘availability and openness’.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7346673 10.54676/EJZH8821 2405685:7GYKP2XC 2405685:BUDHW7MW
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
ZenodoArchiveID: 4706000 previousDOI: 10.5281/zenodo.4706000 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3971656 10.5281/zenodo.4706000 10.53832/edtechhub.0029 2129771:YZIID28Y 2339240:7P4VDPLY 2339240:WYT4QCIW 2405685:85C5HVC7 2405685:I86XXKMH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Guidance Note 12 Ensuring rigorous monitoring and evaluation of initiatives using digital technologies in education for the most marginalised From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684341 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684341 2339240:ZKX9NWUD 2405685:DXSF5ZX6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Tangerine® – Mobile Learning Assessments Made Easy - RTI International (RTI, 2016)
Since 2010, improving early grade reading has been a top priority for RTI and for many bilateral and multilateral donors, including the U.S. Agency for International Development (USAID), The World Bank, UK Aid and others. In support of this work and to improve upon paper forms of assessment, RTI developed a mobile assessment and coaching tool we dubbed Tangerine. Open source for all users, Tangerine is a first-of-its-kind software application optimized for offline data collection on low-cost Android tablets.
Library Catalog: www.rti.org EdTechHub.ItemAlsoKnownAs: 2405685:S8WJWDX2

How solar mini-grids can bring cheap, green electricity to rural Africa - Zajicek, Charlie (odi.org, 2019)
Well-suited to small, remote communities, renewable energy mini-grids can be the most cost-effective option for rural electrification in Africa.
KerkoCite.ItemAlsoKnownAs: 2405685:4VUP32WG 2534378:IT6G3AEW

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph (University of Cambridge, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low per-viewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content. Quantitative investigation into the association between educational television exposure and mathematics capability used nationally representative data, collected by Uwezo Tanzania. A household fixed-effects model showed that exposure to educational television was significantly associated with mathematics capability among children aged 7-16, when controlling for age, sex, school enrolment and Kiswahili attainment. Findings from this model were used in cost-effectiveness calculations, alongside cost data and an estimate of the number of Ubongo Kids viewers. Results compared favourably against those for other interventions, with calculations regarding Ubongo Kids’ ongoing activities suggesting it to have been more cost effective than any other intervention previously investigated using the same cost-effectiveness approach. These findings indicate that in low-income contexts: educational television programmes can aid learning; and, that directing a greater proportion of available educational resources towards educational television interventions may benefit educational outcomes.
KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.54714 10/ghgngw 2405685:5MXCYRXI 2405685:C74MQIKM
Keywords: ___working_potential_duplicate

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

Education for the most marginalised post-COVID-19: Guidance for governments on the use of digital technologies in education – Act one - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684287 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684287 2339240:EXUHD2R4 2405685:VFERK5JK
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
shortDOI: 10/f63z7b KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.01.001 10/f63z7b 2339240:76EQG2NV 2405685:LM7EYD5E 2405685:WU59KPEH 261495:QBFNURGR
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A study of online English language teacher education programmes in distance education context in Pakistan - Farooq, Muhammad U.; Al Asmari, AbdulRahman; Javid, Choudhary Z. (English Language Teaching, 2012)
Technology-based initiatives have transformed the process of teaching and learning activities at formal institutions generally and distance education institutions particularly. Distance education is at the heart of the digital age making maximum use of the emerging technologies. Researchers have favoured computer mediated communications (CMC) for improving the quality of teacher education in developing countries by providing access to more and better educational resources. The researchers designed a CMC-ELT blended model and offered online English language teacher education courses at post-graduate level. A group of students enrolled in MA TEFL programme of Allama Iqbal Open University (AIOU) Islamabad Pakistan, was selected randomly and was guided through CMC-ELT blended model. The results of the study showed that the online support in distance education enhanced students' performance in terms of access, interaction and cost. The effective use of online support in distance education can improve the quality of English language teaching programmes in Pakistan.
Publisher: Canadian Center of Science and Education, 1120 Finch Avenue West Suite 701-309, Toronto, OH M3J 3H7, Canada Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1773213777?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.5539/elt.v5n11p91 2339240:2EBC4XAX 2405685:9V9TWTN7 2405685:ZUW8ZBWE 2534378:6E7C4XSE 2534378:BNLKR978
Keywords: Access to Education; Blended Learning; Computer Mediated Communication; Control Groups; Costs; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Educational Quality; English (Second Language); Experimental Groups; Foreign Countries; Higher Education; Language Teachers; Masters Programs; Online Courses; Open Universities; Pakistan; Postsecondary Education; Pretests Posttests; Program Improvement; Second Language Instruction; Second Language Learning; Statistical Analysis; Student Attitudes; Student Characteristics; Teacher Education Programs; Teaching Methods; __:import:01; __:match:final; __:matched; __:study_id:2096524; __finaldtb

Adverse consequences of school closures - UNESCO (UNESCO, 2020)
School closures - even when temporary - carry high social and economic costs. The disruptions they cause touch people across communities, but their impact is particularly severe for disadvantaged boys and girls and their families. Some of the reasons why school closures are so harmful are listed below. While the list is far from comprehensive, it helps clarify why school closures should matter to all of us. Interrupted learning: Schooling provides essential learning and when schools close, children and youth are deprived opportunities for growth and development.
Library Catalog: en.unesco.org KerkoCite.ItemAlsoKnownAs: 2339240:N9NK3DJF 2339240:UTNECT36 2405685:35ZWVEZ9 2405685:7UZI77DJ

‘6Ps’ audit tool - Rahman, Asad; Carter, Alice (EdTech Hub, 2022)
EdTech interventions so often fail to take into consideration the broader system they work within. EdTech Hub has created this tool to assess interventions and identify any gaps in the thinking that might stop an intervention from working. Keywords: innovation; education system; 6Ps; tool An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0117 2339240:DP8CCUUK 2405685:2FMS5BBU 2405685:58EFZM9F
Keywords: _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
previousshortDOI: 10/ghgng5 previousDOI: 10.5281/zenodo.3762228 EdTechHub.Copy: 2129771:QQWNSYJR EdTechHub.Copy: 2129771:QQWNSYJR shortDOI: 10/ghgng5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 10.53832/edtechhub.0022 10/ghgng5 2129771:QQWNSYJR 2339240:45F2G56T 2405685:3MKIMX34 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

External Validity: Four Models of Improving Student Achievement - Duflo, Annie; Kiessel, Jessica; Lucas, Adrienne (National Bureau of Economic Research, 2020)
Randomized controlled trials in lower-income countries have demonstrated ways to increase learning, in speciﬁc settings. This study uses a large-scale, nationwide RCT in Ghana to show the external validity of four school-based interventions inspired by other RCTs. Even though the government implemented the programs within existing systems, student learning increased across all four models, more so for female than male students, and many gains persisted one year after the program ended. Three of the four interventions had a similar cost eﬀectiveness. The intervention that directly targeted classroom teachers increased the likelihood that teachers were engaged with students.
shortDOI: 10/ghgnd9 KerkoCite.ItemAlsoKnownAs: 10.3386/w27298 10/ghgnd9 2405685:YXBSPAQ7
Keywords: C:Ghana

Early Grade Reading Study II (EGRS II) - USAID (2019)
The activity team works in partnership with the Department of Basic Education to evaluate the efficacy and cost-effectiveness of interventions focused on improving the performance of grade 1 and 2 learners in the subject English First Additional Language.
Library Catalog: www.edu-links.org KerkoCite.ItemAlsoKnownAs: 2405685:FPWA6KU3

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10599846 ZenodoArchiveConcept: 10599845 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1004 2339240:VBH94XQQ 2405685:DJRV7KZW
Keywords: _r:AddedByMyEducationEvidence

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (University of Virginia, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3NFUQ2N5 2339240:7X8NJI23 2339240:AAP9R7UD 2339240:TY3PYSTX 2405685:5IRBQ464 2405685:5J25FLQT 2405685:RQ4ND4UQ 2405685:RVLBVG3I 2405685:YLEQ3IT6
Keywords: ___working_potential_duplicate

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783101 2405685:MIQMEJK2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10652003 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1013 ZenodoArchiveConcept: 10652002
Keywords: _r:AddedByMyEducationEvidence

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
ZenodoArchiveID: 3966976 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3966976 2129771:XMGQ4JQJ 2339240:L5RLM582 2339240:R72E853W 2405685:T2W7MU3K 2405685:U49W6LTF 2405685:ZI8PHKCC
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684327 2339240:J6VCPUDV 2405685:57FXZ5EA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987856 ZenodoArchiveConcept: 10987855 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1022 10.53832/edtechhub.1086 2405685:QEHJZIUB 2405685:S4V6PXXU

World Development Report 2018: Learning to realize education’s promise - World Bank (World Bank Group, 2018)
World Development Report 2018: LEARNING to Realize Education’s Promise
KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-1096-1 2339240:5YCGPE5H 2339240:7URY7SPB 2339240:BFKFTEHP 2339240:HZL7FCFK 2339240:VYNPXJB6 2339240:YM6MIDK7 2405685:7JNTDBCR 2405685:8K4QNUT8 2405685:BF2ZWSJV 2405685:GAYWXIDL 2405685:HQFK65IQ 2405685:HUESCDK5 2405685:JL8R2527 2405685:PZI834WE 2534378:BKV4NR6U
Keywords: C:Low- and middle-income countries

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Nudging in education - Damgaard, Mette Trier; Nielsen, Helena Skyt (Economics of Education Review, 2018)
Can we nudge children, adolescents and their parents to make better decisions on education? And can we nudge teachers to support and encourage better decision making? Education decisions are taken at young ages and involve immediate costs and potential, future benefits. In such settings behavioural barriers (e.g. lack of self-control, limited attention and social norms) likely influence choices and this may motivate the use of low cost ‘nudges’ to gently push behaviour in the desired direction. Our review of nudging interventions shows that while nudging often has positive effects, the greatest effects often arise for individuals affected most by the behavioural barrier targeted by the intervention. Hence understanding underlying behavioural mechanisms is crucial. Negative effects may arise in situations where nudges potentially crowd-out intrinsic motivation, if nudges pressurise individuals, or in situations where the choice architect has an insufficient understanding of behavioural mechanisms.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2018.03.008 2339240:YBXW7W6Z 2405685:TFBCJC4T
Keywords: Behavioural bias; Boost policies; Human capital investment

Guidance Note 1 In the local context — using digital technologies to develop local content From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684307 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684307 2339240:WETE6Y2I 2405685:WWC3MTHS
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Autism screening and diagnosis in low resource settings: Challenges and opportunities to enhance research and services worldwide - Durkin, Maureen S.; Elsabbagh, Mayada; Barbaro, Josephine; Gladstone, Melissa; Happe, Francesca; Hoekstra, Rosa A.; Lee, Li-Ching; Rattazzi, Alexia; Stapel-Wax, Jennifer; Stone, Wendy L.; Tager-Flusberg, Helen; Thurm, Audrey; et al. (Autism Research: Official Journal of the International Society for Autism Research, 2015)
Most research into the epidemiology, etiology, clinical manifestations, diagnosis and treatment of autism is based on studies in high income countries. Moreover, within high income countries, individuals of high socioeconomic status are disproportionately represented among participants in autism research. Corresponding disparities in access to autism screening, diagnosis, and treatment exist globally. One of the barriers perpetuating this imbalance is the high cost of proprietary tools for diagnosing autism and for delivering evidence-based therapies. Another barrier is the high cost of training of professionals and para-professionals to use the tools. Open-source and open access models provide a way to facilitate global collaboration and training. Using these models and technologies, the autism scientific community and clinicians worldwide should be able to work more effectively and efficiently than they have to date to address the global imbalance in autism knowledge and at the same time advance our understanding of autism and our ability to deliver cost-effective services to everyone in need.
KerkoCite.ItemAlsoKnownAs: 10.1002/aur.1575 2339240:VPT8E92I 2405685:ZJU7T2BU
Keywords: Autistic Disorder; Developing Countries; Global Health; Health Services Accessibility; Humans; Internationality; Research; diagnosis; early detection; epidemiology; intervention

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819042 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1043 ZenodoArchiveConcept: 12819041
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Promising practices for equitable remote learning: Emerging lessons from COVID-19 education responses in 127 countries - Dreesen, Thomas; Akseer, Spogmai; Brossard, Matt; Dewan, Pragya; Giraldo, Juan-Pablo; Kamei, Akito; Mizunoya, Suguru; Ortiz, Javier Santiago (UNICEF, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:9MHDW5NY 2339240:FJBQM3KU 2339240:GVM9MG8J 2339240:KXY5ZIUM 2339240:L64HD637 2339240:NNP5XW8Q 2339240:S9X82R99 2339240:UGNM6BJX 2339240:ZTPISV5S 2405685:4BDVYXZK 2405685:4YGQW7GT 2405685:9B3AYRVL 2405685:DE4UMT97 2405685:GIRLDY3C 2405685:MGEDRZ5M 2405685:P246GT26 2405685:PXHHCWS6 2405685:RIGJ57SP 2405685:UAUZXJ9H 2405685:V4TS384A 2405685:ZH65IS2I 2534378:7B4RE4XL 2534379:72F2RW7Y
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Smart buys: system reform, local-level buy-in and reaching the most marginalised - Ndaruhutse, Susy (The Education and Development Forum (UKFIET), 2020)
This blog was written by Susy Ndaruhutse, Chair of the Board of Trustees, UKFIET. Earlier this month, I listened with interest to representatives of the Global Education Evidence Advisory Panel (GEEAP) presenting a summary of the findings and recommendations from their latest report Cost-Effective Approaches to Improve Global Learning: What does recent evidence tell us […]
KerkoCite.ItemAlsoKnownAs: 2339240:S3CPGUIH 2405685:BSJGIH79

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4747475 2405685:RIPJWUDB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Inputs, Incentives, and Complementarities in Education: Experimental Evidence from Tanzania - Mbiti, Isaac; Muralidharan, Karthik; Romero, Mauricio; Schipper, Youdi; Manda, Constantine; Rajani, Rakesh (National Bureau of Economic Research, 2018)
We present results from a large-scale randomized experiment across 350 schools in Tanzania that studied the impact of providing schools with (a) unconditional grants, (b) teacher incentives based on student performance, and (c) both of the above. After two years, we find (a) no impact on student test scores from providing school grants, (b) some evidence of positive effects from teacher incentives, and (c) significant positive effects from providing both programs. Most importantly, we find strong evidence of complementarities between the two programs, with the effect of joint provision being significantly greater than the sum of the individual effects. Our results suggest that combining spending on school inputs (which is the default policy) with improved teacher incentives could substantially increase the cost-effectiveness of public spending on education.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w24876 2339240:6KRPH6ZG 2405685:N3H3SZ7C 4656463:DX4NAZF7

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Beyond the Basics: Improving Post-Primary Content Delivery through Classroom Technology - Beg, Sabrin A; Lucas, Adrienne M; Halim, Waqas; Saif, Umar (National Bureau of Economic Research, 2019)
Using an RCT in middle schools in Pakistan, we test the effect of a government- implemented in-class technology and brief teacher training intervention on student achievement in grade level mathematics and science. After only 4 months of exposure, student's combined math and science score increased by 0.3 standard deviations on both project and government tests, 59 percent more than the control group. Students were also more likely to pass the provincial high-stakes exams. Increased attendance by both students and teachers indicate technology can increase other inputs. At the 200 school scale, this program is extremely cost-effective.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w25704 2339240:8S5BZEQ5 2339240:N3IQ9VDH 2405685:56WJPPUE 2405685:MXHG8QD6
Keywords: EXCLUSION CRITERIA APPLIED; Quality: H; Relevance: M

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

ICT for Education: A Conceptual Framework for the Sustainable Adoption of Technology-Enhanced Learning Environments in Schools - Rodriguez, Patricio; Nussbaum, Miguel; Dombrovskaia, Lioubov (Technology, Pedagogy and Education, 2012)
Currently, the use of information and communication technologies (ICT) in education does not conclusively demonstrate significant effects on learning. However, not all ICT usage models are designed to affect student outcomes. Therefore, to accurately study the impact of ICT, the concept of an educational programme supported by ICT must first be defined. The authors propose the ICT for Education (ICT4E) programme, an evidence-based framework to determine a model's ability to produce improvements before having to evaluate its results. The framework has four components: implementation, intervention, transference and total cost. Based on an explicit definition of the outcomes pursued by a given programme, this framework supports the design of its activities to promote sustainable changes in pedagogical practices in schools and calculate the programme's total cost. The authors illustrate this with a programme implemented in six countries. In Chile, the ICT4E programme forms part of the policy for educational technology, evaluating the effectiveness and scalability of such initiatives. (Contains 3 tables and 3 figures.)
18 citations (Crossref) [2024-02-28] Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2012.720415 2339240:GEJN29VT 2405685:22N8ZU8A
Keywords: Systems Framework; ⛔ No INSPIRE recid found

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

Teaching and Learning Materials Financing - Read, Tony (Where Have All the Textbooks Gone?: Toward Sustainable Provision of Teaching and Learning Materials in Sub-Saharan Africa, 2015)
Suggests that no single universal cause behind the persistent under-financing of textbook provision in Sub-Saharan Africa (SSA) countries exists, but some common components include, (1) the pressure on teaching and learning materials (TLM) budgets caused by rapid enrollment growth; (2) the repeated tendency for curriculum designers to make decisions without taking into account the cost implications on the system as a whole; (3) the failure of development partner (DP) support to addressed affordability and sustainability issues; (4) the misunderstanding of ministries of education (MOEs) and DPs concerning manufacturing versus textbook cost as well as textbook versus system cost; (5) the lack of review and management of the nature and extent of fund diversion, fund misappropriation, piracy, and price mark-ups in undermining allocated TLM funding; and (6) the lack of monitoring, inspection, supervision, and financial audit systems necessary to ensure that all links in the financing and supply chain operate effectively.
KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-0572-1_ch5 2339240:KH9KW2WE 2405685:ZZ9HPXR7

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
15 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 2339240:4VMARDY3 2405685:S4AUFT59
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819000 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1042 ZenodoArchiveConcept: 12818999
Keywords: _r:AddedByMyEducationEvidence

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
EdTechHub.Copy: 2129771:3IIW96ZB shortDOI: 10/gftrqf KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 10/gftrqf 2129771:3IIW96ZB 2339240:AUEREUTT 2339240:NNWXI67C 2339240:QWI89XDJ 2339240:X37484JK 2405685:37II7RPP 2405685:4PBTS4CP 2405685:5LADY8ET 2405685:L36BGXMK 2405685:PT6BTPEC
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Impact of Online Computer Assisted Learning on Education: Evidence from a Randomized Controlled Trial in China - Bai, Yu; Tang, Bin; Wang, Boya; Auden, Emma; Mandell, Blake (Stanford University, 2018)
Education of poor and disadvantaged populations has been a long-standing challenge for education systems in both developed and developing countries. In China, millions of students in rural areas and migrant communities lag far behind their urban counterparts in terms of academic achievement. When they fall behind, they often have no way to catch up. Many of their parents have neither the skills nor the money to provide remedial tutoring; rural teachers often do not have time to give students the individual attention they need. Given this, there is growing interest by both educators and policymakers in helping underperforming students catch up using computer assisted learning (CAL). While CAL interventions have been shown to be effective internationally and elsewhere in China, traditional software-based CAL programs are difficult and costly to implement. An online version of CAL (OCAL), however, may be able to bypass many of offline CAL’s implementation problems and enhance the remedial tutoring experience. Unfortunately, there is little empirical evidence on whether OCAL programs can be effective in improving the quality of rural primary school education in developing countries. The objective of this paper is to examine the impact of an OCAL intervention on the academic and non-academic performance of students and to explore the mechanism behind OCAL’s impact. Importantly, we also aim to assess the cost effectiveness of the new OCAL program versus traditional CAL interventions. To achieve these objectives, we carried out a randomized controlled trial (RCT) involving over 1650 fifth grade students in 44 schools in rural areas and migrant communities across China. Students in the 22 treatment schools attended two 40minute OCAL sessions during their computer class each week for one semester; the students in the other 22 schools were in the control group and did not receive any intervention. According to our findings, OCAL improved overall English scores of students in the treatment group relative to the control group by 0.56 standard deviations. This impact is large when compared with offline CAL programs. We found that OCAL also led to a positive change in the attitudes of students towards English learning and towards student aspirations for their future education level. We found three possible explanations for OCAL’s impact. After rejecting the possibility of the Hawthorne Effect or self-efficacy-induced changes, we believe interest-oriented stimulation is the main source of improvement among students. The chance for comparison and competition with peers, as well as customized remedial question banks tailored to each student’s individual needs, likely contributed to the measured increases in academic performance among students in our sample. Cost-effectiveness analysis showed that the OCAL program is more cost-effective than traditional offline CAL, a comparison which is significant for policymakers as it indicates high potential for OCAL program expansion.
KerkoCite.ItemAlsoKnownAs: 2339240:UVG9KSAI 2339240:ZLVS7CVZ 2405685:7L744UX5 2405685:HM587PSY
Keywords: Quality: H; Relevance: M; ⛔ No DOI found

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students’ learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children’s learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.childyouth.2021.106065 2339240:ZZFSPD7I 2405685:SB69LBNY

EdTech in developing countries: a review of the evidence - Rodriguez-Segura, Daniel (The World Bank Research Observer, 2021)
The emergence of educational technology (“EdTech”) in developing countries has been received as a promising avenue to address some of the most challenging policy questions within educational systems. In this paper, I review and synthesize all existing studies with credible causal identification frameworks of EdTech interventions in developing countries. While other studies review the evidence for EdTech interventions in developed countries, there is currently no equivalent study for developing contexts, in spite of the rising number of studies being produced. I classify studies into four thematic categories based on the type of EdTech intervention analyzed: Access to technology; technology-enabled behavioral interventions; improvements to instruction; and self-led learning. I find that EdTech interventions centered around self-led learning and improvements to instruction are the most effective forms of EdTech at raising learning outcomes. Similarly, technology-enabled behavioral interventions are less promising for generating large effects but highly cost-effective given their typically low marginal costs. Although expanding access to technology alone is not sufficient to improve learning, it is a necessary first step for some other types of interventions. More broadly, the overall success of interventions rests on the thoughtful customization of the EdTech solution to the policy constraints at hand. Finally, EdTech interventions across all thematic areas can and should act as complements by leveraging their respective comparative advantages to address deficiencies within educational systems in developing countries.
KerkoCite.ItemAlsoKnownAs: 10.1093/wbro/lkab011 2339240:DEKZ2C9I 2405685:ZS3CD2X6

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
shortDOI: 10/f7fghr KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 10/f7fghr 2405685:4WTUAF8V 2405685:USCCYKCK 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Does computer-assisted learning improve learning outcomes? Evidence from a randomized experiment in migrant schools in Beijing - Lai, Fang; Luo, Renfu; Zhang, Linxiu; Huang, Xinzhe; Rozelle, Scott (Economics of Education Review, 2015)
The education of the disadvantaged population has been a long-standing challenge to education systems in both developed and developing countries. Although computer-assisted learning (CAL) has been considered one alternative to improve learning outcomes in a cost-effective way, the empirical evidence of its impacts on improving learning outcomes is mixed. This paper uses a randomized field experiment to explore the effects of CAL on student academic and non-academic outcomes for students in migrant schools in Beijing. Our results show that a remedial CAL program held out of regular school hours improved the student standardized math scores by 0.15 standard deviations and most of the program effect took place within 2 months after the start of the program. Students with less-educated parents benefited more from the program. Moreover, CAL also significantly increased the students’ interest in learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2015.03.005 2339240:4J6WADM5 2405685:3LTP3SLM
Keywords: China; Computer-assisted learning; Development; Education; Migration; Random assignment; Test scores

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
ZenodoArchiveID: 4706019 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706019 2339240:D85SY35R 2405685:SMLIMS2X
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1046 ZenodoArchiveConcept: 13117630
Keywords: _r:AddedByMyEducationEvidence

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=108296506&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 2339240:B8GCJR9U 2405685:7W777384 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

Challenges Facing Adoption of Information Communication Technology (ICT) In Educational Management in Schools in Kenya - Kipsoi, Emmy; Chang'ach, Dr; Sang C, Hellen (Journal of Sociological Research, 2012)
ICT has contributed greatly to educational management in schools globally (Zhao and Frank, 2003). However, in Kenya schools hardly use ICTs to manage the quality of output, or to raise teacher productivity, or to reduce costs through analyzing spending. This is attributed to a myriad of challenges facing most schools in Kenya with regard to adoption of ICTs in educational management. This has resulted to a slow rate of adoption of technology despite its promise and potential for use in educational management in schools. As such, this paper analyses the lethargy that has surrounded education management in schools with respect to acquisition of Information Communication Technology. Education and training sector has a major role to play in the implementation of the proposed ICT policy. First, the sector itself is a major user of ICT, not only in education, training and research but also in the management of the sector. The paper argues that ICT policies must be dynamic, cost-effective, adaptable, and differentiated between sectors and between the various segments of educational management in order to contribute effectively to education management. The recommendations of this paper provide a basis for the urgent need for the integration of ICTs in educational management in schools in Kenya.
KerkoCite.ItemAlsoKnownAs: 10.5296/jsr.v3i1.1882 2339240:RXCIEA2R 2405685:EMUX9EK9

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students' learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children's learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.childyouth.2021.106065 2339240:YF7YC22M 2405685:DWQ4UZX5
Keywords: Adjustment; COVID-19; Education; Learning Strategies; Learning loss; Pakistan; Pandemics; School Dropout; School Dropouts; School Learning

Strategies for reducing inequalities and improving developmental outcomes for young children in low-income and middle-income countries - Fernald, Lia; Alderman, Harold; Behrman, Jere; O'Gara, Chloe; Yousafzai, Aisha; Cabral de Mello, Meena; Hidrobo, Melissa; Ulkuer, Nurper; Ertem, Ilgi; Iltus, Selim (Lancet, 2011)
This report is the second in a Series on early child development in low-income and middle-income countries and assesses the effectiveness of early child development interventions, such as parenting support and preschool enrolment. The evidence reviewed suggests that early child development can be improved through these interventions, with effects greater for programmes of higher quality and for the most vulnerable children. Other promising interventions for the promotion of early child development include children's educational media, interventions with children at high risk, and combining the promotion of early child development with conditional cash transfer programmes. Effective investments in early child development have the potential to reduce inequalities perpetuated by poverty, poor nutrition, and restricted learning opportunities. A simulation model of the potential long-term economic effects of increasing preschool enrolment to 25% or 50% in every low-income and middle-income country showed a benefit-to-cost ratio ranging from 6·4 to 17·6, depending on preschool enrolment rate and discount rate.
shortDOI: 10/bphz4m KerkoCite.ItemAlsoKnownAs: 10.1016/S0140-6736(11)60889-1 10/bphz4m 2339240:U6FXSTXG 2405685:7F469WAJ 2405685:7F5HTSH8 4803016:YIU4VCUY

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
ZenodoArchiveID: 4706036 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706036 2339240:CB8D4LUQ 2339240:METE88UD 2339240:MK55NVDC 2339240:Z3EF9Q75 2405685:3XIBJD8G 2405685:3Y33YNL3 2405685:8JZVGC6W 2405685:HBXKVKMA 2405685:QJ783WH5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.07.002 2339240:MXTDK768 2405685:K9AQNHDY
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

Can free primary education meet the needs of the poor?: evidence from Malawi - Kadzamira, Esme; Rose, Pauline (International Journal of Educational Development, 2003)
Following elections in 1994, the Government of Malawi embarked on an ambitious programme of free primary education (FPE), resulting in a dramatic increase in enrolment. The paper argues that the policy did not sufficiently consider the ways in which direct and indirect costs of schooling continue to be prohibitive for some households, or the effects that the expansion would have on quality. The relevance of education for the majority of children who receive only a few years of primary schooling is also questioned. The paper suggests that FPE might not be contributing to the achievement of poverty alleviation goals, as intended.
KerkoCite.ItemAlsoKnownAs: 10.1016/S0738-0593(03)00026-9 2339240:RHFDRS6C 2405685:KNBRX6T6
Keywords: Development; Educational policy; Gender; International education; Malawi; Poverty

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684325 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684325 2339240:KRAUGIY3 2405685:3KMQRBG7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Place: Bridgetown Publisher: University of the West Indies KerkoCite.ItemAlsoKnownAs: 2339240:H5SC64NG 2405685:HNDKMF9C 2534378:5F2RLGL3 2534378:783739U4
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found

School’s Out: Experimental Evidence on Limiting Learning Loss Using “Low-Tech” in a Pandemic - Angrist, Noam; Bergman, Peter; Matsheng, Moitshepi (National Bureau of Economic Research, 2020)
Schools closed extensively during the COVID-19 pandemic and occur in other settings, such as teacher strikes and natural disasters. This paper provides some of the first experimental evidence on strategies to minimize learning loss when schools close. We run a randomized trial of low-technology interventions – SMS messages and phone calls – with parents to support their child. The combined treatment cost-effectively improves learning by 0.12 standard deviations. We develop remote assessment innovations, which show robust learning outcomes. Our findings have immediate policy relevance and long-run implications for the role of technology and parents as partial educational substitutes when schooling is disrupted.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w28205 2339240:IJXPSRFF 2339240:IRQDPEL7 2405685:8XJARTV7 2405685:LHBGNCNF 2405685:YHH4SI2X 2534379:I69U33PS
Keywords: ___working_potential_duplicate

Women's empowerment in action: Evidence from a randomized control trial in Africa - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (American Economic Journal: Applied Economics, 2020)
We evaluate a multifaceted policy intervention attempting to jump-start adolescent women's empowerment in Uganda by simultaneously providing them vocational training and information on sex, reproduction, and marriage. We find that four years postintervention, adolescent girls in treated communities are more likely to be self-employed. Teen pregnancy, early entry into marriage/cohabitation, and the share of girls reporting sex against their will fall sharply. The results highlight the potential of a multifaceted program that provides skills transfers as a viable and cost-effective policy intervention to improve the economic and social empowerment of adolescent girls over a four-year horizon.
KerkoCite.ItemAlsoKnownAs: 10.1257/app.20170416 2339240:BW3HX5HC 2405685:ZQIFS8C9 4656463:WCISNIER
Keywords: Child Care; Children; Domestic Abuse; Fertility; Education and Economic Development; Marriage; Family Planning; Family Structure; Human Development; Income Distribution; Labor Productivity; Economic Development: Human Resources; Marital Dissolution; Migration; Non-labor Discrimination; Labor Demand; Human Capital; Occupational Choice; Skills; Youth; Economics of Gender

Innovation in education: what works, what doesn’t, and what to do about it? - Serdyukov, Peter (Journal of Research in Innovative Teaching & Learning, 2017)
Purpose The purpose of this paper is to present an analytical review of the educational innovation field in the USA. It outlines classification of innovations, discusses the hurdles to innovation, and offers ways to increase the scale and rate of innovation-based transformations in the education system. Design/methodology/approach The paper is based on a literature survey and author research. Findings US education badly needs effective innovations of scale that can help produce the needed high-quality learning outcomes across the system. The primary focus of educational innovations should be on teaching and learning theory and practice, as well as on the learner, parents, community, society, and its culture. Technology applications need a solid theoretical foundation based on purposeful, systemic research, and a sound pedagogy. One of the critical areas of research and innovation can be cost and time efficiency of the learning. Practical implications Several practical recommendations stem out of this paper: how to create a base for large-scale innovations and their implementation; how to increase effectiveness of technology innovations in education, particularly online learning; how to raise time and cost efficiency of education. Social implications Innovations in education are regarded, along with the education system, within the context of a societal supersystem demonstrating their interrelations and interdependencies at all levels. Raising the quality and scale of innovations in education will positively affect education itself and benefit the whole society. Originality/value Originality is in the systemic approach to education and educational innovations, in offering a comprehensive classification of innovations; in exposing the hurdles to innovations, in new arguments about effectiveness of technology applications, and in time efficiency of education.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/JRIT-10-2016-0007 2339240:H2BGZB69 2405685:R3REETEJ
Keywords: Educational technology; Implementation; Innovation; Time efficiency

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117639 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1048 ZenodoArchiveConcept: 13117638
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117643 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1049 ZenodoArchiveConcept: 13117642
Keywords: _r:AddedByMyEducationEvidence

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102397 2339240:6FG39EY3 2339240:LB3VWRGN 2405685:7MUIIRXU
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Large Learning Gains in Pockets of Extreme Poverty: Experimental Evidence from Guinea Bissau - Fazzio, Ila; Eble, Alex; Lumsdaine, Robin L; Boone, Peter; Bouy, Baboucarr; Hsieh, Pei-Tseng Jenny; Jayanty, Chitra; Johnson, Simon; Silva, Ana Filipa (2021)
Children in many extremely poor, remote regions are growing up illiterate and innumerate despite high reported school enrollment ratios. Possible explanations for such poor outcomes include demand – for example, low perceived returns to education compared to opportunity cost; and supply – poor state provision and inability of parents to coordinate and finance better schooling. We conducted a cluster-randomized trial in rural Guinea Bissau to understand the effectiveness and cost of concerted supply-based interventions in such contexts. Our intervention created simple schools offering four years of education to primary-school aged children in lieu of the government. At endline, children receiving the intervention scored 58.1 percentage points better than controls on early grade reading and math tests, demonstrating that the intervention taught children to read and perform basic arithmetic, from a counterfactual condition of very high illiteracy. Our results provide evidence that particularly needy areas may require more concerted, dramatic interventions in education than those usually considered, but that such interventions hold great potential for increasing education levels among the world’s poorest people.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jpubeco.2021.104385 2339240:DAU6XEE6 2405685:FSYXBS55 4656463:NYQXYQP2

Remote Learning: Evidence from Nepal during COVID-19 - Radhakrishnan, Karthika; Sabarwal, Shwetlena; Sharma, Uttam; Cullen, Claire; Crossley, Colin; Letsomo, Thato; Angrist, Noam (World Bank, 2021)
This note discusses early results from a distance education program on foundational numeracy for primary school students in Nepal during Coronavirus (COVID-19) evaluated in a randomized trial. The trial included 3,700 households with children in public school (grades 3-5). It provided support for foundational numeracy through mobile phone-based tutoring. The trial tested delivery through public school teachers and also through NGO facilitators. It led to a 30 percent increase in foundational numeracy, with teachers being slightly more effective at producing learning gains than NGO facilitators. These results suggest that instructional support through mobile phones can be a high-access and low-cost approach to providing instruction at scale
Accepted: 2021-07-28T17:29:14Z KerkoCite.ItemAlsoKnownAs: 2339240:LFIQ9LIB 2405685:F89QL28Q
Keywords: Coronavirus; Covid-19; Numeracy; Pandemic Impact; Remote Learning; School Closure

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792765 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1126 ZenodoArchiveConcept: 15792764
Keywords: _r:AddedByMyEducationEvidence

Open Content - Haßler, Björn; Mays, Tony (The International Encyclopedia of Digital Communication and Society, 2014)
Open content is typically digital content that allows broader use than traditionally printed or copyrighted content. Open content is freed up content, for instance through permissive licensing, such as Creative Commons. Open content includes open educational resources (OER), OpenCourseWare (OCW), open video, open access publications, as well as open data. It shares some similarity with open source software. Open content can have different freedoms, such as legal freedom, technological freedom (including usability and accessibility), as well as freedom in terms of education and participation, related to inclusion and interactive pedagogy. More broadly open content is related to open education and open educational practices. Although open content can be traced back further, the movement developed particularly rapidly in the 2000s, with major education and research stakeholders publishing open content and adopting policies promoting open content and open research practices. This entry reviews the origins of open content, and discusses different aspects of “open.” Two specific areas are highlighted: first, open content in higher education, including open textbooks, massively open online courses, open video, and research on open content, pointing to cost savings; second, open educational resources in Africa through recent developments and success stories, particularly in the context of OER Africa.
EdTechHub.Source: 2129771:FY5V62YE shortDOI: 10/ghgnfs KerkoCite.ItemAlsoKnownAs: 10.1002/9781118767771.wbiedcs154 10/ghgnfs 2129771:FY5V62YE 2339240:SH85QKLX 2339240:UQM5RELF 2405685:3SMZ333H 2405685:A8LVRMQR 2405685:L6CQTXAK 2405685:UP7P7L2D 2405685:Z2N7IQ6J 2405685:Z2W75XMJ
Keywords: Author:Haßler; _C:Canada CAN; _C:France FRA; _C:South Africa ZAF; _C:Spain ESP; _C:United Kingdom GBR; __C:scheme:1; dode_eth-src-dode; dode_eth-trf2-dode; open access; open education; open educational resources

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
ZenodoArchiveID: 4706074 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706074 2339240:8TCJQBLC 2405685:5DWI862Y 2405685:ZWLE9BLR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Short and Long-Run Distributional Impacts of COVID-19 in Latin America - Lustig, Nora; Martinez Pabon, Valentina; Neidhöfer, Guido (2021)
We simulate the short- and long-term distributional consequences of COVID-19 in the four largest Latin American economies: Argentina, Brazil, Colombia and Mexico. We show that the shortterm impact on income inequality and poverty can be very significant, but that additional spending on social assistance more than offsets the effect in Brazil. The offsetting effect is significant in Argentina and Colombia, and nil in Mexico where there has been no such expansion. We find that a universal basic income that would have produced the same reduction in the poverty gap as actual policies would have cost slightly more but would have benefited the poor (the nonpoor) slightly less (more). To project the long-term consequences, we estimate the impact of the pandemic on school achievement and its intergenerational persistence. We use information on school closures, educational mitigation policies, and account for educational losses related to health shocks and parental job loss. Our findings show that in all four countries the impact is strongly asymmetric and affects particularly the high-school completion rates of children from disadvantaged families. Our simulations suggest that mitigation policies seem to have a minor impact on containing these negative effects.
KerkoCite.ItemAlsoKnownAs: 2339240:TURVV9V3 2405685:R7SG8FJ4

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
ZenodoArchiveID: 4705912 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705912 2339240:26FUGGA3 2339240:X339ME8R 2405685:EHKCNED4 2405685:NIVS5RZF 2405685:TWMVIX77
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Promoting Student–Teacher Interactions: Exploring a Peer Coaching Model for Teachers in a Preschool Setting - Johnson, Stacy R.; Finlon, Kristy J.; Kobak, Roger; Izard, Carroll E. (Early Childhood Education Journal, 2017)
Peer coaching provides an attractive alternative to traditional professional development for promoting classroom quality in a sustainable, cost-effective manner by creating a collaborative teaching community. This exploratory study describes the development and evaluation of the Colleague Observation And CoacHing (COACH) program, a peer coaching program designed to increase teachers’ effectiveness in enhancing classroom quality in a preschool Head Start setting. The COACH program consists of a training workshop on coaching skills and student-teacher interactions, six peer coaching sessions, and three center meetings. Pre-post observations of emotional support, classroom organization, and instructional support using the Classroom Assessment Scoring System of twelve classrooms assigned to peer coaching were compared to twelve control classrooms at baseline and following the intervention. Findings provide preliminary support that the peer coaching program is perceived as acceptable and feasible by the participating preschool teachers and that it may strengthen student–teacher interactions. Further program refinement and evaluation with larger samples is needed to enhance student–teacher interactions and, ultimately, children’s adaptive development.
shortDOI: 10/gbjks7 KerkoCite.ItemAlsoKnownAs: 10.1007/s10643-016-0790-1 10/gbjks7 2405685:5SRMZ3SD
Keywords: Classroom quality; Head Start; Peer coaching; Professional development; Professional learning communities; Student–teacher interactions

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.
KerkoCite.ItemAlsoKnownAs: 2339240:TTB8Z79I 6018420:4TZJWG3F

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Teacher Performance-Based Incentives and Learning Inequality - Filmer, Deon; Habyarimana, James; Sabarwal, Shwetlena (Rise Programme, 2020)
This study evaluates the impacts of low-cost, performance-based incentives in Tanzanian secondary schools. Results from a two-phase randomized trial show that incentives for teachers led to modest average improvements in student achievement across different subjects. Further, withdrawing incentives did not lead to a “discouragement effect” (once incentives were withdrawn, student performance did not fall below prebaseline levels). Rather, impacts on learning were sustained beyond the intervention period. However, these incentives may have exacerbated learning inequality within and across schools. Increases in learning were concentrated among initially better-performing schools and students. At the same time, learning outcomes may have decreased for schools and students that were lower performing at baseline. Finally, the study finds that incentivizing students without simultaneously incentivizing teachers did not produce observable learning gains.
KerkoCite.ItemAlsoKnownAs: 2405685:KH5WR8A6 2561267:PWZSY59G
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819139 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1045 ZenodoArchiveConcept: 12819138
Keywords: _r:AddedByMyEducationEvidence

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How behavioral science can empower parents to improve children's educational outcomes - Bergman, Peter (Behavioral Science & Policy, 2019)
Parents powerfully influence their children’s educational outcomes. Yet psychological and informational barriers impede parents’ ability to engage with their children in ways that improve outcomes: parents tend to have inflated perceptions of their children’s performance, which can deter them from taking helpful steps to effectively support their learning, and parenting is complex. Limited cognitive bandwidth for coping with complexities can steer parents’ attention away from actions that have long-term benefits for their children and toward actions yielding immediate returns. Poor school-to-parent communication and poverty exacerbate all of these problems. In this article, the author demonstrates how providing timely, actionable information to parents can lower these barriers and help parents engage with their children more productively from kindergarten through high school. Moreover, providing this information can improve educational outcomes at low cost.
KerkoCite.ItemAlsoKnownAs: 10.1353/bsp.2019.0004 2339240:EFP32JJ7 2405685:W5PIX5JE

Are Teacher Absences Worth Worrying About in the U.S.? - Clotfelter, Charles; Ladd, Helen; Vigdor, Jacob (National Bureau of Economic Research, 2007)
Using detailed data from North Carolina, we examine the frequency, incidence, and consequences of teacher absences in public schools, as well as the impact of an absence disincentive policy. The incidence of teacher absences is regressive: schools in the poorest quartile averaged almost one extra sick day per teacher than schools in the highest income quartile, and schools with persistently high rates of teacher absence were much more likely to serve low-income than high-income students. In regression models incorporating teacher fixed effects, absences are associated with lower student achievement in elementary grades. Finally, we present evidence that the demand for discretionary absences is price-elastic. Our estimates suggest that a policy intervention that simultaneously raised teacher base salaries and broadened financial penalties for absences could both raise teachers' expected income and lower districts' expected costs.
KerkoCite.ItemAlsoKnownAs: 10.3386/w13648 2405685:3JQ59PN4 2486141:IUEZS4NI

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Disrupting education? Experimental evidence on technology-aided instruction in India - Muralidharan, Karthik; Singh, Abhijeet; Ganimian, Alejandro J. (American Economic Review, 2019)
We study the impact of a personalized technology-aided after-school instruction program in middle-school grades in urban India using a lottery that provided winners with free access to the program. Lottery winners scored 0.37 sigma higher in math and 0.23 sigma higher in Hindi over just a 4.5-month period. IV estimates suggest that attending the program for 90 days would increase math and Hindi test scores by 0.6 sigma and 0.39 sigma respectively. We find similar absolute test score gains for all students, but much greater relative gains for academically-weaker students. Our results suggest that well-designed, technology-aided instruction programs can sharply improve productivity in delivering education.
shortDOI: 10/ggqfkz KerkoCite.ItemAlsoKnownAs: 10.1257/aer.20171112 10/ggqfkz 2339240:2URYXAL4 2339240:4YAVCBCF 2339240:7V3XB7ZJ 2339240:8LAH5EZS 2339240:FPI5PFGU 2339240:QRHQXRYZ 2339240:U2V8LTLL 2339240:V85IRLNH 2405685:7WM44UJQ 2405685:AJVTKPNE 2405685:EKZSBGYG 2405685:EWWJF7S6 2405685:EZDRM9UV 2405685:HDWKAHGN 2405685:MADAMGDT 2405685:N2HAMNQ9 2405685:SYASQJ2L 2405685:YFXKBCTF 2534378:JMN7CGMF
Keywords: Analysis of Education; Returns to Education; Education: Government Policy; Human Capital; Human Development; Income Distribution; Labor Productivity; Economic Development: Human Resources; Migration; Occupational Choice; Quality: H; Relevance: H; Skills; _THEME: Teacher Professional Development; ___working_potential_duplicate; ⛔ No DOI found

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Conducting Semi-Structured Interviews - Adams, William C. (Handbook of Practical Program Evaluation, 2015)
Conducted conversationally with one respondent at a time, the semi-structured interview (SSI) employs a blend of closed- and open-ended questions, often accompanied by follow-up why or how questions. About one hour is considered a reasonable maximum length for SSIs in order to minimize fatigue for both interviewer and respondent. This chapter begins with a discussion on the disadvantages and advantages of SSIs. Despite the disadvantages and costs of SSIs, they offer some extraordinary benefits as well. Semi-structured interviews are superbly suited for a number of valuable tasks, particularly when more than a few of the open-ended questions require follow-up queries. The chapter presents some recommendations that can be considered when constructing an SSI guide. All in all, effectively conducted semi-structured interviews, even though labor intensive, should be worth the effort in terms of the insights and information gained.
Section: 19 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119171386.ch19 KerkoCite.ItemAlsoKnownAs: 10.1002/9781119171386.ch19 2339240:69ZTFIC2 2405685:VQD9I55K
Keywords: SSI guide; open-ended questions; semi-structured interviews

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.
shortDOI: 10/gfw2mk KerkoCite.ItemAlsoKnownAs: 10.1080/2331186X.2016.1139439 10/gfw2mk 2405685:K8ZKUDQE

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 2339240:WQ3SA2IB 2405685:JTHYW3X4
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 2339240:JZZE3QML
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Influence of mobile learning training on pre-service social studies teachers' technology and mobile phone self-efficacies - Gloria, Adedoja; Oluwadara, Abimbade (Journal of Education and Practice, 2016)
Current instructional deliveries favour the use of mobile technology because of its inherent potentials and benefits such as portability, ease of use cost and others. Despite these benefits, many teachers especially in Sub-Saharan Africa still prefer the conventional method and use mobile phones for social engagements such as texting, chatting, callings and others. Though, these teachers use mobile phones for these social activities, using it for instruction is somewhat problematic for them without adequate training on its pedagogical implications. This is also because there are dearth of trainings in this area. Some factors that could however affect this type of specialised training include Technology Self-efficacy, Mobile Phone Self-efficacy, attitude, age and others. The sample of this present study was 101 pre-service social studies teachers in two Universities in Nigeria. The influence of the Mobile learning training on Technology/Mobile Phone Self-efficacies was explored. The results indicated that the pre-service social studies teachers have high Technology/Mobile Phone Self-efficacies after exposure to the training.
Publisher: IISTE, No 1 Central, Hong Kong Island, Hong Kong SAR KerkoCite.ItemAlsoKnownAs: 2405685:2B3XKEGJ 2405685:MNN95GGK 2534378:GD8S4UHN 2534378:KAL73UF6 2534378:SDN92DUR
Keywords: Age Differences; ERIC; Current Index to Journals in Education (CIJE); Electronic Learning; Foreign Countries; Higher Education; Instructional Effectiveness; Likert Scales; Nigeria; Postsecondary Education; Predictor Variables; Preservice Teachers; Pretests Posttests; Questionnaires; Self Efficacy; Social Studies; Student Teacher Attitudes; Technological Literacy; Technology Education; __:import:01; __:match:final; __:matched; __:study_id:2096188; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Cloud computing architecture for eLearning in secondary schools - Mwakisole, Kennedy; Kissaka, Mussa; Mtebe, Joel (The African Journal of Information Systems, 2019)
In recent years, schools have been investing heavily on information and communications technology (ICT) infrastructure to implement eLearning systems to enhance the quality of education in secondary schools in Tanzania. The majority of these systems are implemented using a traditional web-based eLearning approach on school premises which is costly and limits usage due to lack of scalability and flexibility. Consequently, many schools have started adopting cloud computing as a solution. However, this adaption depends on well-defined cloud eLearning architecture. This study proposed cloud architecture for implementing an eLearning system in secondary schools in Tanzania by adopting various layers proposed in previous studies. The effectiveness of this proposal was evaluated by comparing its performance with a similar traditional web-based eLearning system using the Moodle benchmark tool and Apache Jmeter. The study found that eLearning systems implemented in the cloud-based infrastructure had better performance metrics than web-based eLearning systems on school premises.
KerkoCite.ItemAlsoKnownAs: 2339240:H37DIS7E 2405685:QILWRT8Y
Keywords: ⛔ No DOI found

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.
KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.10.1.780 2339240:27J8DKI6 2405685:AYFYMSM8

Towards a framework for the use of ICT in teacher training in Africa - Unwin, Tim (Open Learning: The Journal of Open, Distance and e-Learning, 2005)
There is a gulf between the rhetoric of those advocating the use of ICT in education in Africa and the reality of classroom practice. This paper explores some of the reasons for this, and outlines a possible framework for the successful implementation of teacher training programmes that make advantageous use of appropriate ICTs. It argues that six fundamental principles of good practice must be addressed for such programmes to be effective: a shift from an emphasis on ‘education for ICT’ to the use of ‘ICT for education’; an integration of ICT practice within the whole curriculum; a need for integration between pre‐service and in‐service teacher training; a need for the development of relevant and locally produced content; a need for appropriate educational partnerships; and an emphasis on the development of sustainable costing models. The paper concludes with a framework for action to deliver the very real benefits of ICT for teacher training in Africa.
Publisher: Routledge _eprint: https://doi.org/10.1080/02680510500094124 Extra URL: https://doi.org/10.1080/02680510500094124 KerkoCite.ItemAlsoKnownAs: 10.1080/02680510500094124 2339240:KKN62XAA 2405685:JJX3EQD5
Keywords: Africa; Education policy; ICT; Teacher training

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5795656 10.53832/edtechhub.0079 2405685:5XBMPDX6
Keywords: _r:AddedByZotZen

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Artificial Intelligence in Education. Posters and Late Breaking Results, Workshops and Tutorials, Industry and Innovation Tracks, Practitioners, Doctoral Consortium and Blue Sky, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-36336-8_119 2339240:EWGWHJXK 2339240:SL8MC9DM 2405685:FG4XFKKM 2405685:MYQJA7TD

EdTech for Learning in Emergencies and Displaced Settings: A rigorous review and narrative synthesis - Tauson, Michaelle; Stannard, Luke (Save The Children, 2018)
Globally, according to UNESCO (2017), 264 million children of primary and secondary school age are out school. UNESCO also estimates that worldwide roughly 100 million young people are fully illiterate. While data on attendance, enrolment, and literacy can be difficult to gather in fragile and conflict-affected settings, estimates suggest that children in these settings are roughly three times more likely to be out of school than children living in stable, but low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:39QITWJZ 2339240:6F23G9BX 2339240:CX7MJW5R 2339240:D26Y5JXH 2339240:FBAM53IG 2339240:FBCFVAEE 2339240:FHZXSRXI 2339240:G8GRKFFX 2339240:KL87UZMA 2339240:NRUBXTAT 2339240:RHDU25IK 2339240:SLJGQQ9G 2405685:28WH3URF 2405685:2YFK36CZ 2405685:6QS8CQ9G 2405685:9QNHP33B 2405685:9ZFQ6L5J 2405685:CMAMJWTI 2405685:H2SWIIEB 2405685:JJQTKVY2 2405685:KETBQUYZ 2405685:KLHB3S5G 2405685:NSWYZQA7 2405685:PF7AX4UZ 2405685:X2N4NZRQ 2405685:YG9HXGM8 2534378:WMLTBU37
Keywords: GENERAL - to be categorised; Google Scholar/ forced displacement edtech; IMPORT_FROM_DFID_RITE; Important; Read; _THEME: Teacher Professional Development; ___working_potential_duplicate; auto_merged; ⛔ No INSPIRE recid found

An Overview of ICT for Education of Refugees and IDPs - Joynes, Chris; James, Zoe (K4D, Knowledge, Evidence, and Learning for Development, 2018)
This rapid review examined examples of ICT approaches to address the education needs of those living in IDP and refugee camps and lessons learned from these experiences. Although ICT is considered a good system to fulfil the education needs within refugee settings, many studies conclude that access to ICTs in schools or at home is not sufficient to improve learning outcomes. It is due to the role of a mentor or tutor figure is seen as key to productive learner engagement with technology, and the effectiveness of ICT-based education is reliant on appropriate teacher training to ensure successful up-take at the classroom level (Tauson & Stannard 2018: 47, 62; UNESCO 2018: 74; Carlson 2013: 30). Secondly, in terms of content, ICTs for education should provide content that is responsive or adaptable to the learners’ level, is implemented in line with the local curriculum and also is relevant to the learners’ context (Tauson & Stannard 2018: 36-38, 61). Despite this potential for ICTs, there remains a broad lack of evidence related to education in refugee settings (Burde et al. 2015; Tauson & Stannard 2018; World Bank 2016). In particular, more information is needed on pedagogic design, on the effective use of ICTs for learning, on the role of ICTs in ensuring continuity of and linkages between learning in formal and non-formal settings, on the role of ICTs in educational data-gathering, and on the cost-effectiveness of ICT-led interventions (Burde et al 2015; Tausin & Stannard 2018; Carlson 2013). In light of the availability of evidence, some of the studies cited here instead supplement their findings by drawing on observational studies, and on studies on effective ICT usage from learners in non-refugee contexts (Burde et al. 2015; Tauson & Stannard 2018).
KerkoCite.ItemAlsoKnownAs: 2339240:75ZRE2RA 2339240:J9VYGNUA 2339240:N4VI3AHC 2405685:3Z2JBF58 2405685:UUEEVW9Z 2405685:VSQUMYUI
Keywords: Google Scholar/ "education technology" refugees; RER theme_general; RER theme_pedagogies and modalities; ⛔ No DOI found

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.spasta.2022.100679 2405685:EQ9TER5R 4042040:8UF2BKAH
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4279156 10.5281/zenodo.4279156 2129771:XYEJSVYW 2339240:59XYS4NB 2339240:EETQSD8S 2339240:HZTGKNN9 2405685:2W6A2G3H 2405685:6KDDB8UA 2405685:MS5GH9KJ 2405685:S9MFQ8KB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117635 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1047 ZenodoArchiveConcept: 13117634
Keywords: _r:AddedByMyEducationEvidence

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Low-connectivity Educational Technology: A Case Study of Supporting Learning during Covid-19 via SMS with ‘Keep Kenya Learning’ - Jordan, Katy; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (Journal of Learning for Development, 2024)
The use of Short Messaging Service (SMS) for education has grown in recent years, drawing particular attention to supporting school-level learners, due to the Covid-19 pandemic. This renewed interest has prompted questions about how this form of educational technology could be used in the longer term. However, despite being used in many Covid-19 responses, there are few documented examples of innovative applications in this field during the pandemic, which represents a gap in the literature. As a medium for education, SMS offers potential benefits such as being cost-effective and having positive impacts on learning. In this paper, we present a case study of an educational programme rapidly implemented during the pandemic as part of the ‘Keep Kenya Learning’ program, to support learners remotely in terms of literacy, numeracy, and social and emotional learning topics. Through the case study, we describe the innovative process used to rapidly develop content for SMS, and draw upon usage statistics, quiz scores and user feedback to gain insights into its implementation with learners and caregivers in Kenya. The case study demonstrated that educational television content can be effectively adapted to mobile delivery. Furthermore, we present practical reflections on the development and implementation of SMS educational technology which will help inform future initiatives. These include considering timing in relation to school terms when planning a supporting intervention, and designing content in a modular way to allow flexibility for learners in navigating through courses.
KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v11i3.1066 2405685:BWBWSFY4

Supporting equitable access to learning via SMS in Kenya: Impact on engagement and learning outcomes - Jordan, Katy; Myers, Christina; Damani, Kalifa; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (British Journal of Educational Technology, 2024)
Abstract The use of SMS messaging for education has grown in recent years, with particular attention recently during the Covid‐19 pandemic. Mobile phones often have high levels of ownership in low‐income contexts compared to computers, and lower connectivity requirements, which arguably make this a more equitable medium than data‐heavy online instruction, for example. However, given that gender can be a factor to influence mobile device access and use, it is also important to consider educational applications through a gender lens, to avoid further exacerbating digital divides. In this paper, we present an analysis of server log and evaluation data in relation to a literacy‐focused initiative for primary‐aged learners carried out in Kenya as part of the Tusome programme and through the SMS‐based M‐Shule education platform, which does not require an Internet connection or smartphone to run. The extent of engagement with the platform varies according to gender and location within the country. The data also demonstrate a positive impact on learning outcomes regardless of learners' gender and location. Furthermore, the learning gains are shown to be relatively cost‐effective in comparison with educational technology interventions in similar contexts. The findings show that this low‐connectivity adaptive model has a positive impact on learning outcomes. It is a scalable approach to support a range of learners in Kenya, providing more support to learners who need it, and leading to increased foundational learning outcomes overall. As such, the findings will also be of highly relevant to other low‐connectivity contexts. Practitioner notes What is already known about this topic Mobile phones can be used as a means to support learning, through mobile learning and SMS, particularly in low‐connectivity contexts, although there is a lack of rigorous evidence of impact upon learning outcomes. Mobile phone device ownership tends to be higher than computer or wired Internet connections in many low‐income contexts. Software applications which adapt to the learners' level have shown good potential for gender‐equitable learning outcomes in low‐income contexts; however, these often require an Internet connection in addition to computers or tablets to be run on. What this paper adds There is a lack of contextually relevant evidence of the impact of SMS‐based mobile learning applications in low‐resource and low‐connectivity contexts upon learning outcomes. Through analysis of data generated via an experimental design, this study provides evidence that literacy materials delivered through an SMS‐based educational platform—M‐Shule—can have a positive impact upon learning outcomes. Furthermore, gains are equitable in terms of learners' gender, and location, within Kenya. Implications for practice and/or policy Mobile phones can be an effective way of reaching learners to provide additional educational support as part of existing education programmes in low‐connectivity environments. Learning gains using M‐Shule are evidenced as significant and relatively cost‐effective. Existing high‐quality learning materials developed in other media can be effectively adapted to SMS to reach learners particularly who are out‐of‐school or during periods of educational disruption.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13533 2405685:JQREWVZC

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11652091 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1032 ZenodoArchiveConcept: 11652090
Keywords: _r:AddedByMyEducationEvidence

The Use of Information and Communication Technology (ICT) for Knowledge Management in the Second Cycle Educational Institutions in Ghana - Ohemeng, Patrick; Twum, Edward; Nii, Isadore (International Journal of Computer Applications, 2015)
Given its capabilities to widen access, improve the quality and reduce the cost of developing, accessing and maintaining information, Information and Communication Technology (ICT) offers increased possibilities for managing knowledge. This paper thus investigates the level of utilization of ICT in the knowledge management processes in the Ghanaian educational system. Being a descriptive study, a randomly selected sample of second cycle educational institutions was surveyed through questionnaire. Using descriptive data analysis, the study found a low level of Information and Communication Technologies usage in knowledge management processes in the second cycle educational system. Knowledge management practices were found to be inefficient due to, among other things, absence of strategic policies and nonutilization of ICT. The findings indicate that the Secondary Schools are not deriving the efficiency returns of the computers they have acquired due to the absence of a deliberate and effective strategy for knowledge management. Also students, teachers and administrators in the second cycle schools are not benefitting from the information revolution for knowledge management. It was recommended that capacity building in knowledge management and improvement of Internet speed should be given priority attention by educational authorities.
KerkoCite.ItemAlsoKnownAs: 10.5120/ijca2015906600 2339240:MY59MT5E 2405685:R9EMPF5Y

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Artificial intelligence for strengthening healthcare systems in low- and middle-income countries: A systematic scoping review - Ciecierski-Holmes, Tadeusz; Singh, Ritvij; Axt, Miriam; Brenner, Stephan; Barteit, Sandra (npj Digital Medicine, 2022)
In low- and middle-income countries (LMICs), AI has been promoted as a potential means of strengthening healthcare systems by a growing number of publications. We aimed to evaluate the scope and nature of AI technologies in the specific context of LMICs. In this systematic scoping review, we used a broad variety of AI and healthcare search terms. Our literature search included records published between 1st January 2009 and 30th September 2021 from the Scopus, EMBASE, MEDLINE, Global Health and APA PsycInfo databases, and grey literature from a Google Scholar search. We included studies that reported a quantitative and/or qualitative evaluation of a real-world application of AI in an LMIC health context. A total of 10 references evaluating the application of AI in an LMIC were included. Applications varied widely, including: clinical decision support systems, treatment planning and triage assistants and health chatbots. Only half of the papers reported which algorithms and datasets were used in order to train the AI. A number of challenges of using AI tools were reported, including issues with reliability, mixed impacts on workflows, poor user friendliness and lack of adeptness with local contexts. Many barriers exists that prevent the successful development and adoption of well-performing, context-specific AI tools, such as limited data availability, trust and evidence of cost-effectiveness in LMICs. Additional evaluations of the use of AI in healthcare in LMICs are needed in order to identify their effectiveness and reliability in real-world settings and to generate understanding for best practices for future implementations.
Number: 1 Publisher: Nature Publishing Group KerkoCite.ItemAlsoKnownAs: 10.1038/s41746-022-00700-y 2405685:MMYGXG48 2486141:99IMTN2W
Keywords: Health policy; Translational research

An interactive math braille learning application to assist blind students in Bangladesh - Nahar, L; Sulaiman, R; Jafaar, A (Assistive Technology, 2020)
Due to the lack of affordable assistive tools for learning mathematics, blind students in Bangladesh still use outdated learning tools like Tailor Frame. Therefore, demand for a low-cost technological tool is there that will help the blind students to learn math braille and calculate numbers more easily. To provide an effective and affordable assistive tool, this study begins with a needs assessment study to identify the basic needs of blind students in learning math braille and solving mathematical calculations. Afterward, a mobile phone based interactive assistive application is proposed to improve the learning facilities of math braille using Nemeth code for blind students in Bangladesh. Interfaces of the application are designed based on their needs. Besides, interaction methods (such as, hearing & touching) of blind students with the physical world were another criterion in designing very interactive interfaces that provide self-learning facilities. The interfaces are evaluated by the teachers, experts, and end users in order to identify the usability. The evaluation shows a promising result toward the acceptability of the designed application. Therefore, this application can be helpful for the blind students to learn math braille using Nemeth Code.
KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2020.1734112 10/gkm64j 2339240:9H367DU5 2405685:9SMEBFMC

Evidence Coaching Handbook - Rahman, Asad (EdTech Hub, 2024)
This handbook captures EdTech Hub's approach to providing evidence coaching on the EdTech Hub Evidence-Led Entrepreneurship Course. Individuals and organisations who support EdTech entrepreneurs to scale their products impactfully (e.g., accelerators, entrepreneurship programmes, funders) can all provide evidence coaching to entrepreneurs. This Handbook is for anyone working within an EdTech startup, or an entrepreneur who wants to better apply evidence to key decisions. By sharing EdTech Hub’s approach and process for evidence coaching, we hope to nurture a more evidence-led EdTech entrepreneurship ecosystem, leading to more EdTech products that scale sustainably, and help children to read, write, and count. The Handbook contains EdTech Hub’s five-step process for generating and applying evidence as a startup, with specific tools we used along the way. The process is a guide for others to adapt and tailor to their unique context and challenges. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255915 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1051 ZenodoArchiveConcept: 13255914
Keywords: _r:AddedByMyEducationEvidence

Challenge and srivers of over-Enrollment in the early years of primary school in Uganda - Weatherholt, Tara; Jordan, Rachel; Crouch, Luis; Barnett, Ed; Pressley, Jennifer (International Journal of Early Childhood, 2019)
Consistent over-enrollment, together with low official repetition rates, in the early years of school indicates inaccurate reporting of repetition, which may mask the reasons for low primary school completion. Actual repetition rates may be higher and pose issues for teachers through overcrowding of classrooms and issues for governments through inefficient education systems. This research explores repetition rates of students in Primary 1 in Uganda and considers the implications for efficiency and quality of education for the early years of school. The sample comprised 1440 students in Primary 1 classrooms in 120 schools. Interviews were conducted with 1318 caregivers of randomly selected students and 1439 teachers of the same students, and official records from 118 schools were examined to compare age and repetition rates. Findings showed that caregiver- and teacher-reported repetition is much higher than officially reported by schools; that repetition is strongly linked to non-attendance in pre-primary schooling; and that caregivers reported more over-age students, fewer target-age students, and more under-age students than official school records. Policy implications include the need for dialogue around repetition rates and the possible efficiency effects of less-costly, pre-primary education on the total primary schooling cycle.
KerkoCite.ItemAlsoKnownAs: 10.1007/s13158-019-00238-3 2339240:3WMYLF8F 2405685:975JWM6R 4656463:2HX448CB
Keywords: Early childhood; Education efficiency; Low-income countries; Pre-primary education; Repetition

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgk65 previousDOI: 10.5281/zenodo.3830951 shortDOI: 10/ghgk65 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3830951 10.5281/zenodo.3830951 10.53832/edtechhub.0030 10/ghgk65 2339240:2AU72ZG2 2339240:3DWURGVT 2339240:KMTF4A22 2339240:L86PMYJ2 2339240:PRSHWWK5 2405685:4TKSDH2I 2405685:97JHVZU9 2405685:GUJ3TBS3 2405685:NA8X7J9C 2405685:S3EKNHHG 2405685:XGAFJNAD 4656463:PU6FSTAF
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence

Experimenting with Automatic Text-to-Diagram Conversion: A Novel Teaching Aid for the Blind People - Mukherjee, Anirban; Garain, Utpal; Biswas, Arindam (Journal of Educational Technology & Society, 2014)
ABSTRACT Diagram describing texts are integral part of science and engineering subjects including geometry, physics, engineering drawing, etc. In order to understand such text, one, at first, tries to draw or perceive the underlying diagram. For perception of the blind students such diagrams need to be drawn in some non-visual accessible form like tactile graphics. Technologies for producing tactile graphics are available but they are too expensive to be afforded by the blind students or schools in developing countries like India. As a result, science education for a large population of blind students is severely compromised. This paper proposes a novel solution to this problem. A method for digital to Braille mapping of geometry diagrams on the low-cost traditional Braille text printer is reported here. Later on, this is integrated with a previously developed text-to-diagram conversion system. Using the integrated system, a blind student can input a geometry word problem and perceive the underlying diagram on a Braille printout. The major part of the study involves rigorous evaluation of the system at a Blind school. The enthusiasm and the ability shown by the subjects in using the system strongly attest its viability as an effective teaching/learning tool for the blind students.
KerkoCite.ItemAlsoKnownAs: 2339240:PALXABSW 2405685:QC4QNMYJ
Keywords: ⛔ No DOI found

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4924787 10.53832/edtechhub.0131 2405685:D7JX8S7S
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
previousshortDOI: 10/ghgk69 previousDOI: 10.5281/zenodo.3911651 shortDOI: 10/ghgk69 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911651 10.53832/edtechhub.0034 10/ghgk69 2339240:4SKXJ887 2405685:ED7RBJHG 2405685:VSMMBMQE
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

STEM Skills Initiatives for Adolescent Girls in the LAC Region - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin Moss (EdTech Hub, 2022)
This report was produced in response to a request from the UNICEF country office of Argentina and presents a curated list of science, technology, engineering, and mathematics (STEM) skills initiatives for adolescent girls in the Latin American and Caribbean (LAC) region. It also provides an introduction to gender equality and background on the participation of women in STEM fields in the LAC region — as well as cross-cutting recommendations based on an analysis of a series of initiatives. Key words: STEM; Gender; Girls; LAC; Argentina; technology; Science An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6402444 10.53832/edtechhub.0085 2405685:I8GTEI7T 2405685:MFYZUPKU
Keywords: F: Helpdesk response; _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 ZenodoArchiveConcept: 10893091 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 2405685:Z7XKA7E8
Keywords: _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15737188 ZenodoArchiveConcept: 15737187 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1124 2405685:WNGITGKP
Keywords: _r:AddedByMyEducationEvidence

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14172051 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1069 ZenodoArchiveConcept: 14172050
Keywords: _r:AddedByMyEducationEvidence

Social media use by undergraduate students of education in Nigeria: a survey - Wickramanayake, Lalith; Muhammad Jika, Saidu (The Electronic Library, 2018)
Purpose This paper aims to investigate teacher students’ perceptions, intentions, experiences, attitudes, opinions and barriers concerning social media use and impact of social media on their learning process. Design/methodology/approach A stratified sampling technique was applied to draw the sample, and 242 teacher students were selected as a sample from three higher educational institutions in Gombe State, Nigeria. A questionnaire survey method was used to collect the data. Data analysis was by means of simple and inferential statistics. Findings The students widely used mobile phones to access social media, and social media was extremely popular for education, entertainment and communication among them. Educational and informational communities were also preferred by students to other social media communities. The study further revealed that effective social media usage among students enhanced their different types of skills including learning. Unstable electricity connections, security and privacy issues, internet costs and unreliable internet connections were recorded as some barriers concerning students’ social media use. Originality/value The outcome of this study will be a unique contribution because the pertinent literature provides little evidence or research highlights concerning teacher students’ social media use. Even more, the results of the present study may be a useful resource for university administrators, education policymakers and innovative teachers in universities – especially in developing countries and particularly Nigeria – when considering integration of modern techniques and technologies with university teaching and learning.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/EL-01-2017-0023 2339240:AGAUINHT 2405685:PISZZ6ZX
Keywords: Internet-based learning; Media-based teaching; Nigeria; Social media; Teaching students; User studies

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118401 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1025 ZenodoArchiveConcept: 11118400
Keywords: _r:AddedByMyEducationEvidence

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China's elementary schools. To do so we analyze results from three randomized field experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The field experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China's rural areas and migrant communities, there is reason to believe that computer based learning can benefit both girls and boys equally. This finding has possible implications for China's ongoing efforts to integrate computers and computing technologies into the nation's underserved schools.
shortDOI: 10/f4g6qc KerkoCite.ItemAlsoKnownAs: 10.1016/j.compedu.2012.08.011 10/f4g6qc 2339240:MK5NR7LT 2405685:6XU8AFCQ 2405685:JJ2NC7PA
Keywords: Country-specific developments; Elementary education; Evaluation of CAL systems; Gender studies; Teaching/learning strategies

Growth prospects, market challenges and policy measures: Evolution of mobile broadband in Pakistan - Hanif, Muhammad Shehzad; Yunfei, Shao; Hanif, Muhammad Imran (Digital Policy, Regulation and Governance, 2018)
Purpose The paper aims to explore the long-term prospects of mobile broadband adoption in a developing country. The supply-side and demand-side policy measures are recommended to counter the challenges to broadband adoption. Design/methodology/approach Methodologically, this study uses document analysis to explain secondary data including growth statistics, trade literature and previous scholarly research. Based on the growth statistics of broadband and the informed market insights, the research discusses the prevailing market threats and recommends counter measures to improve the long-term prospects of broadband propagation. Findings The growth of mobile broadband is settling down in Pakistan due to various barriers like cost, literacy, security and unavailability of local content. Collaborative efforts are required by the government, the service providers and the people to enhance the adoption of broadband service and secure economic benefits of the broadband. Practical implications The research offers useful implications for managers and policymakers in Asian and African developing countries; the policy measures discussed here may serve as guidelines for them in the design of their own policies regarding broadband supply and demand. Originality/value The study makes an effort to examine the broadband growth in a developing country on the basis of both quantitative and qualitative aspects. The research endeavors to fill the gap on the particular scholarship of research covering potential uptake of broadband services and the effects of constraining elements to broadband adoption in a developing country.
KerkoCite.ItemAlsoKnownAs: 10.1108/DPRG-04-2017-0014 2339240:SGX3L6KS 2405685:5KV4NF9R

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China’s elementary schools. To do so we analyze results from three randomized ﬁeld experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The ﬁeld experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China’s rural areas and migrant communities, there is reason to believe that computer based learning can beneﬁt both girls and boys equally. This ﬁnding has possible implications for China’s ongoing efforts to integrate computers and computing technologies into the nation’s underserved schools.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.compedu.2012.08.011 2339240:5UDBDTWD 2405685:RZVXC9AE

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Responding to autism in low and middle income countries (LMIC): What to do and what not to do - McConkey, Roy (Brain Sciences, 2022)
Autism is a spectrum disorder that occurs globally with increasing numbers of children and adults being identified with this condition. Although rates are higher in more affluent nations, the bulk of people with autism reside in Low and Middle Income Countries (LMICs). However, most do not have access to timely and appropriate support. The types of services delivered in high income countries are often ill-suited to the needs and resources of LMICs. Rather alternative forms of provision need to be devised. In common with other public health initiatives, these should be family-focused and community based, with suitably qualified and experienced leaders who in turn train and supervise a cadre of knowledgeable support workers drawn from local communities and cultures. As well as providing personalized, home-based guidance to people with autism and to their primary carers, regular group-based advocacy and training activities are undertaken in partnership with available mainstream services such as schools and social services. The principles and operations of these new forms of services are described in this paper albeit with an acknowledgment of their limitations. In recent decades, the cost-effectiveness of these approaches have been demonstrated with other chronic illnesses and disabling conditions in LMICs but their extension to autism has barely begun. More affluent countries are being forced to adopt similar strategies in response to the increased numbers of people identified with autism. A transformation in research strategies is essential to building better international support for persons with autism.
KerkoCite.ItemAlsoKnownAs: 10.3390/brainsci12111475 2339240:332RE5XB 2405685:LK436A6Z

The last mile in school access: Mapping education deserts in developing countries - Rodriguez-Segura, Daniel; Kim, Brian Heseung (Development Engineering, 2021)
With recent advances in high-resolution satellite imagery and machine vision algorithms, fine-grain geospatial data on population are now widely available: kilometer-by-kilometer, worldwide. In this paper, we showcase how researchers and policymakers in developing countries can leverage these novel data to precisely identify “education deserts” – localized areas where families lack physical access to education – at unprecedented scale, detail, and cost-effectiveness. We demonstrate how these analyses could valuably inform educational access initiatives like school construction and transportation investments, and outline a variety of analytic extensions to gain deeper insight into the state of school access across a given country. We conduct a proof-of-concept analysis in the context of Guatemala, which has historically struggled with educational access, as a demonstration of the utility, viability, and flexibility of our proposed approach. We find that the vast majority of Guatemalan population lives within 3 km of a public primary school, indicating a generally low incidence of distance as a barrier to education in that context. However, we still identify concentrated pockets of population for whom the distance to school remains prohibitive, revealing important geographic variation within the strong country-wide average. Finally, we show how even a small number of optimally-placed schools in these areas, using a simple algorithm we develop, could substantially reduce the incidence of education deserts in this context. We make our entire codebase available to the public – fully free, open-source, heavily documented, and designed for broad use – allowing analysts across contexts to easily replicate our proposed analyses for other countries, educational levels, and public goods more generally.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.deveng.2021.100064 2405685:RIEFMI2C 4042040:NKVNSSIM
Keywords: Access to education; Education deserts; Education in developing countries; School placement

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Providing access to education in Sub-Saharan countries through Content-Oriented technology - Kiboro, Angelica; Bailey, Sheena; Nair, Mrinay; Salam, Tomisin; Dwhytie, Alex (2014 IEEE Canada International Humanitarian Technology Conference - (IHTC), 2014)
Access to education has been a growing concern for children in developing economies, namely lack of access to quality customized online content in the classroom and at home; lack of tools that make learning fun and effective in key subject areas; and lack of state resources to meet educational demands. The Rumie Initiative was founded to tackle these concerns. It is a non-profit organization bringing educational content to the world's underprivileged children through low-cost technology. The Rumie Initiative's vision is to redefine the way education is provided, and through this, significantly reduce poverty and drive economic development. The primary advantage of The Rumie Initiative over all other educational technology solutions is that its content is specifically tailored to meet the local educational needs and curriculum standards. Utilizing the vast reserves of free online updated educational content available today; these android driven tablets are an affordable and intuitive way to deliver pre-loaded content without the requirement of internet access. Through mass global volunteerism, The Rumie Initiative collaborates with educators in choosing appropriate educational content and distributes content-loaded tablets through local Non-Governmental Organizations, communities and government entities. The Rumie Initiative has started a program of trials around the world and recently received a positive response at a Computer - Based Math Education Summit in New York hosted by UNICEF from November 21st to 22nd 2013. The initiative was first launched in Haiti on 25th October 2013 and has since, been gaining momentum, currently exploring opportunities in Sub-Saharan countries such as Ghana, Kenya, Uganda, Rwanda, Burundi, South Africa and Nigeria. This paper focuses on The Rumie Initiative's unique business model to reach the masses, emphasizing issues relating to the power of volunteer ism, the forging of strategic development partners, and content-oriented technologies in increasing access to education.
ISSN: null KerkoCite.ItemAlsoKnownAs: 10.1109/ihtc.2014.7147542 10/ggn3tg 2339240:5H77UWY6 2405685:XF5UPDR7
Keywords: Blogs; Communities; Education; Internet; Internet access; Monitoring; Organizations; Rumie initiative; Servers; Terminology; authorisation; computer aided instruction; content management; content-oriented technology; curriculum standards; economics; economies; educational content; educational demands; government entities; non-governmental organizations; online content; standards; sub-Saharan countries

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803111 10.53832/edtechhub.0075 2339240:XBN27377 2405685:674LJ8EY 2405685:EW94QPAA
Keywords: _r:AddedByZotZen

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7314047 ZenodoArchiveConcept: 7314046 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7314047 10.53832/edtechhub.0152 10.53832/edtechhub.1024 2405685:99ZRGDBB 2405685:NMJMENAG
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

A framework for an ICT-based development program for science teachers in state universities and colleges in region VI - Magallanes, Amel Lavezores; Lavezores, Amel (Universal Journal of Educational Research, 2014)
Curriculum reform is central to the aspirations of many developing countries as they strive to deliver a quality education to their citizens. In State Universities and Colleges in Region VI, with its remarkable achievement of a high literacy rate in a few decades, the next step is bringing its resources to bear on providing a quality education so that Filipino science professors and students may take their places in the global labor force. This study concerns the integration of information and communications technologies (ICT) into the science curriculum of Higher Education Institutions in State Universities and Colleges in the Philippines particularly in Region VI, and the training and development requirements of science professors in this regard. A mixed methodology was employed to obtain qualitative data from 11 policy makers as represented by the Vice President of Academic Affairs of the SUC's in region VI, and quantitative data from a questionnaire for which 139 replies were received from SUC's science professors in Region VI.The findings of this study confirmed those citations in the literature that inefficient management planning and inadequate resources influence the integration of ICT in the science curriculum. Furthermore, the qualitative and quantitative findings confirmed that teachers' access to training is affected by time constraints, ineffective ICT course material, unavailability of ICT infrastructures and facilities, and high cost of ICT trainings. The policy makers interviewed in this study perceived the teachers as having a positive attitude toward ICT integration in the science curriculum, quantitative data from the teachers pointed to a high interest in ICT integration, and their willingness to pursue further professional development in the effective use of ICT in the science curriculum. Furthermore, age factor exhibited a significant difference in ICT skills, utilization and individual barriers of science teachers in SUC's Region VI. The length of service also showed a very significant difference as to the ICT skills, utilization attitudes, and individual barriers of the teacher respondents. However, as to their gender and highest educational attainment, home location and school location, there was no such factor implicating a non-significant difference in the attitudes, skills, utilization and perceived barriers.
Publisher: Horizon Research Publishing, 506 North Garfield Avenue #210, Alhambra, CA 91801 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1697502673?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2014.020909 2405685:FXQZCGHG 2534378:CCZ6ZKIL
Keywords: Barriers; College Faculty; College Science; Computer Literacy; Computer Uses in Education; ERIC; Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Information Technology; Mixed Methods Research; Philippines; Postsecondary Education; Science Teachers; State Colleges; State Universities; Teacher Attitudes; Technology Integration; Training

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.
Num Pages: 18 Publication Title: ActionAid KerkoCite.ItemAlsoKnownAs: 2339240:4FGB56K3 2405685:53CECDLI

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:2M2HXSJN 2405685:SNDDADWB 2405685:SNTV94NA 2534378:7FFHYISA 2534378:ASX6DAFV 2534378:WH9M9DZM
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

Interactive Radio Instruction: An Update from the Field - Bosch, Andrea; Rhodes, Rebecca; Kariuki, Sera (Education Development Center, 2002)
Interactive radio instruction (IRI), a methodology developed to turn a typically one-way technology into a tool for active learning in and outside the classroom, continues to be an attractive educational strategy in developing countries after almost 30 years. The original model for IRI math, created in Nicaragua by a team from Stanford University in the early 1970s, sought to combine the low cost and high reach of the radio medium and a clear understanding of how people learn. Since that time, 20 countries around the world have developed IRI programs for a variety of subjects, audiences, and learning environments, many of which have been sustained for up to 10 years and counting. The methodology has been expanded and adapted to include different levels of math, science, health, English, Spanish and Portuguese, environmental education, early childhood development, and adult basic education for learners of all ages. In each case, the series has been designed specifically by local specialists to be engaging and to meet learning objectives in that country. After three decades, interest in IRI does not seem to be waning. (See the Annex at the end of this chapter for a list of IRI projects and their current status.) This chapter updates earlier information about interactive radio instruction over the past five years, and introduces two cases where IRI has had an impact in Africa in two ways not captured in the past.1 In Guinea, IRI has gone to scale on an unprecedented level in West Africa to reach students and teachers on a national level. The Guinean IRI series is integrated with teacher development initiatives and is used in almost all primary schools across the nation, with 880,000 students. In Zambia, a new IRI series is being developed that reaches out to students who otherwise would be without schools, and have become increasingly vulnerable due to poverty and the HIV/AIDs. This example shows how IRI can be used effectively to overcome obstacles of access in Africa and to increase the chances that students can receive an education. These examples show how IRI retains its core elements, yet continues to evolve to meet new educational and social challenges.
KerkoCite.ItemAlsoKnownAs: 2339240:NJJTZUJS 2405685:PNRBAXJM

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4780972 2405685:4UQT8WRN 2405685:WWUQ7VRT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen

Digital literacy for children — 10 things to know - UNICEF (2019)
Digital literacy goes beyond technical know-how. It refers to the knowledge, skills and attitudes that allow children to be both safe and empowered in an increasingly digital world. This encompasses their play, participation, socializing, searching and learning through digital technologies. What constitutes digital literacy will vary according to children’s age, local culture and context. Children need to be digitally literate even when they are not online. Facial scanning and artificial intelligence-based profiling increasingly affect children’s lives. Children’s schooling, social welfare and future job opportunities may depend on how well they understand the digital world around them. Digital literacy is a growing part of any approach to skills development. It features in UNICEF’s framework which seeks to prepare children and adolescents for school, work and life. In addition to digital literacy, other interconnected skills for UNICEF are: foundational skills (literacy and numeracy); transferable skills (also known as life skills, 21st-century skills or soft skills); and job-specific skills (technical and vocational skills). Tools to develop and assess digital literacy are proliferating. A number of digital competence frameworks have been developed by both international agencies and companies. Frameworks are a necessary starting point as they define the boundaries of what constitutes digital literacy and inform curricula and assessments. Despite using a range of labels (e.g. digital literacy, skills, citizenship), they broadly converge around the idea of a set of competencies that include technical as well as transferable skills, such as communication and problem solving. Yet most existing tools place little emphasis on children. Digital literacy definitions usually focus on citizens of all ages and not on children specifically. UNICEF believes there is a need to focus more on digital literacy for children, who have unique needs. In this area, there is a slow change from a risk and safety paradigm towards rights-based approaches that favour expression, play and development. Few programmes operate at scale or have been evaluated for impact. One contributing factor is the lack of global consensus and standards that makes it difficult for governments and other stakeholders to design and implement comparative and cost-effective initiatives, especially within developing countries. Similarly, UNICEF programmes would benefit from greater coordination. While UNICEF has delivered a range of digital literacy programmes at the request of governments, a survey of 40 initiatives carried out by 37 Country Offices shows they are not well coordinated with each other, and knowledge is not systematically generated or shared about efficacy and impact. Implementing digital literacy is not easy. According to the Country Offices surveyed, key barriers to digital literacy programming are: lack of teachers’ and trainers’ capacity; lack of ICT infrastructure; low connectivity (especially for remote areas); and a lack of understanding from decision-makers. The Country Offices are asking for policy development support, digital literacy frameworks, curriculum guidelines and practical tools, such as training manuals and toolkits. Some existing digital literacy frameworks or tools suit UNICEF well. These include the DigComp framework of the European Commission and the Digital Kids Asia-Pacific framework developed by the UNESCO Asia and Pacific Regional Office in Bangkok. If using existing digital literacy frameworks, UNICEF can add value by focusing on children. Digital literacy programmes should be context-driven. Implementing digital literacy programmes effectively requires more than simply importing a good programme from elsewhere. Beyond choosing a framework, an integrated approach to digital literacy involves undertaking a preliminary diagnostic review of the local context, developing operationalization guidelines and conducting impact assessments.
KerkoCite.ItemAlsoKnownAs: 2339240:DAVC5T72 2405685:LGV5JGFE

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PX8LX2HD 2405685:HWT67YS2 2405685:MUSAVHQ9

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7510031 ZenodoArchiveConcept: 7510030 KerkoCite.ItemAlsoKnownAs: 2129771:K9HHIYYP 10.5281/zenodo.7510031 10.53832/edtechhub.0156 2405685:B8SQMMBA
Keywords: _r:AddedByZotZen

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FY4BHGH3

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Teachers need training and support, not just an internet connection, to deliver quality distance education - Conover, Anna C (Teacher Task Force, 2022)
This blog is based on the findings of Distance learning and teacher training strategies. Lessons from the Caribbean, a recently published report by the Teacher Task Force. It was written by Anna C. Conover, Consultant Distance teaching and learning have expanded rapidly around the world since COVID-19 school closures first began in 2020. The transition exposed a wide digital divide in many countries, where lack of access to devices, online content and internet connectivity hindered universal access. Equally crucial, the shift shone a light on the need for more and better teacher training in digital and relevant pedagogical skills. However, in spite of this urgent need, ministries of education in many countries are only now integrating ICT competencies and standards into teacher policy frameworks. Moreover, traditional teacher training programmes do not necessarily adequately cover digital and related pedagogical skills in initial teacher training and continuing professional education. Teacher training can help improve learners’ and teachers’ experience of distance learning In response to the demand for training in distance learning and technology integration in small island developing states (SIDS) in the Caribbean, the Distance Learning and Teacher Training Strategies in the Caribbean SIDS teacher training programme was created to enhance the capacity of national education systems. The Teacher Task Force, UNESCO’s Global Education Coalition, Blackboard, the Caribbean Centre for Educational Planning (CCEP), UNICEF Jamaica, and the German Federal Ministry for Economic Cooperation and Development collaborated to develop, implement and monitor the programme. Building on the 2020 pilot project, Professional Development for Teachers for Blended Learning and Online Strategies, the programme was designed to strengthen teachers’ digital and related pedagogical skills. It took a holistic and context-sensitive approach to strengthening teachers’ capacity to guarantee that the most vulnerable students were not left behind during the crisis. The project aimed to confront challenges such as: how to maintain engagement and interaction for learning; how to convert content into appropriate online learning formats; how to handle school management issues, such as the need to respect normal school hours; and how to work with students with diverse needs. Providing support in these areas also helped to address teachers’ psychosocial well-being, since the abrupt transition to online teaching led to significant disruption of teachers’ professional and personal lives, causing uncertainty and other emotional challenges. Careful course design, adaptable materials and supportive communities of practice are essential for successful distance learning A key lesson from the programme was the importance of high standards for course design, content, and capacity for collaboration and delivery. Online platforms or learning management systems must be intuitive and user-friendly; courses must include different forms of interaction and student-teacher feedback loops; and time and space must be allotted for collaboration, reflection and experimentation. Since parental involvement is important for successful distance learning, course design should also include guidance for parents and reliable channels for them to communicate with teachers. Preparing and adapting materials for online learning is one of the most challenging and time-consuming tasks for teachers in transitioning to distance learning. So, teacher training should include guidance on tools to facilitate this work, such as “live worksheets”, which are interactive and support assessment at a distance. And programmes should use open-source materials where possible, or explicitly state copyright conditions when needed, to increase scalability and enable teachers to re-use materials. Teachers who participated in the teacher training programme particularly appreciated being part of a community of practice, enabling them to make new connections with distance education experts and other teachers in similar situations across their country and region. This feeling of belonging to a supportive network, as well as their newly acquired skills, boosted their personal and professional confidence in applying digital technologies and the required skills in their classrooms. Teacher training for distance education should prepare teachers to create inclusive online learning environments Ensuring inclusive education should be a priority in distance learning. Even though this form of schooling can limit teachers’ interactions with students (e.g., by reducing opportunities for spontaneous communication and gestural cues), it can also provide opportunities to promote inclusion. Designing courses with accessibility in mind is essential to create inclusive learning environments. For instance, to accommodate the needs of learners with disabilities, participants should be given a range of ways to access materials and participate in courses. This may include offering asynchronous* and synchronous** options for discussion, multimodal (visual, aural, textual, etc.) delivery of content, and downloadable as well as livestreamed content. In multilingual contexts, adapting to teachers’ language needs is also essential. In the SIDS programme, course content was often only available in French or English. However, to allow participants to conduct discussions in the language with which they were most comfortable, course facilitators allowed participants to form online breakout groups using other languages. Flexibility is a key feature in planning for teacher training Training teachers for distance education must be flexible, since teachers have competing and sometimes unforeseen demands on their time. Course content, pacing and assignments should be adjusted throughout the course according to participants’ changing needs. This is particularly important during emergency situations. For accreditation transparency and to maintain teacher motivation, courses can adapt to teachers’ time constraints by offering different levels of certification and micro-credentials for specific ICT skills. Careful planning that considers school calendars and teachers’ accessibility needs, as well as good communication campaigns, are essential to ensure successful enrolment and sustained attendance in teacher training. Registration should be easy and obstacle-free, and directly available online. In general, teacher training should not be scheduled at the beginning or at the end of the school year when teachers are busiest, or during long summer vacations when many teachers are not available. Partnerships are important for developing teacher training programmes for distance education Partnerships are particularly important in delivering distance education, since it requires considerable expertise and resources, including costly devices, uninterrupted connectivity, education software, open educational resources, and pedagogical and organizational expertise. Given that connectivity and device availability are often a barrier in online education, governments and stakeholders should develop partnerships with technology companies and internet providers to identify solutions, while ensuring that data security and participant privacy are respected. Educational technologies have proven to be useful to ensure continuity of education in emergency situations. Increasingly true to all societies, they are also among the basic tools needed to fully participate in our contemporary world. However, investing in these technologies will not achieve the desired results unless we also invest in teachers’ digital and related pedagogical skills. Initial and in-service teacher education must therefore be re-imagined including these skills and technologies. With their first-hand experience of the challenges and opportunities of remote teaching, teachers must be involved in the design, implementation and monitoring of distance learning and technology integration. In such a way, they must effectively be placed at the heart of wider education transformation. Glossary *Asynchronous online learning: Education and learning that occur online at a different time compared to when the teacher is instructing. **Synchronous online learning: Education and learning that occur online at the same time, but not in the same place with teachers and/or other learners. Photo credit: Abir Roy Barman/Shutterstock.com
KerkoCite.ItemAlsoKnownAs: 2339240:FW56SP6K 2405685:5SMBTHW9

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7306712 ZenodoArchiveConcept: 7306711 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7306712 10.53832/edtechhub.0132 2405685:ACLTCQV2 2405685:XIIQ4FSE
Keywords: _r:AddedByZotZen